Non-aqueous electrolyte and non-aqueous electrolyte battery using the same

By using cyclic anhydrides and sulfonate compounds with specific structures in non-aqueous electrolyte batteries, the problems of capacity loss and increased internal resistance in high temperature environments are solved, and the safety and durability of the battery are improved.

JP2025019125AInactive Publication Date: 2025-02-06MITSUBISHI CHEM CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024202049
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-06
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing non-aqueous electrolyte batteries have problems such as large capacity loss, large gas generation and increased internal resistance in high temperature environments, especially in large-scale equipment such as automobiles, which have insufficient safety and durability.

Method used

Using a non-aqueous electrolyte with a specific structure, including a specific structure cyclic anhydride and a specific structure sulfonate compound, the constituent materials of the battery are optimized to reduce capacity loss and gas generation during high temperature storage.

Benefits of technology

After high temperature storage, the non-aqueous electrolyte battery exhibits small capacity loss, small amount of gas generation and increased internal resistance, which improves the safety and durability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025019125000001
    Figure 2025019125000001
  • Figure 2025019125000002
    Figure 2025019125000002
  • Figure 2025019125000003
    Figure 2025019125000003
Patent Text Reader

Abstract

To provide a highly safe non-aqueous electrolyte battery that exhibits small capacity loss, small amount of gas generation, and small increase in resistance after high-temperature storage.SOLUTION: Non-aqueous electrolyte for a lithium ion secondary battery (excluding those containing CF2HCOOCH3), includes: at least one compound (1) selected from the group consisting of succinic anhydride, maleic anhydride, and allyl succinic anhydride; and at least one compound (2) selected from the group consisting of LiFSO3, LiCH3SO3, and LiCF3SO3. In the non- aqueous electrolyte, the ratio (α / β) of the mass (α) of compound (1) to the mass (β) of compound (2) is 0.01 or more and 50 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a nonaqueous electrolyte and a nonaqueous electrolyte battery using the same. [Background technology]

[0002] Lithium nonaqueous electrolyte secondary batteries, which use a lithium-containing transition metal oxide as a positive electrode and a nonaqueous solvent as an electrolyte, can achieve high energy density and are therefore used in a wide range of applications, from small power sources for mobile phones and laptop computers to large power sources for automobiles, railways, and load leveling. However, in recent years, there has been an increasing demand for higher performance for nonaqueous electrolyte batteries, and there is a strong demand for improvements in various characteristics.

[0003] For example, Patent Document 1 describes that a nonaqueous electrolyte secondary battery having improved electrochemical characteristics over a wide temperature range can be obtained by using an electrolyte that contains two or more specific cyclic carbonates and contains a specific cyclic acid anhydride bonded to a side chain having three or more carbon atoms and a double bond or triple bond at an end thereof in the nonaqueous electrolyte. Patent Document 2 describes that by adding a specific fluorosulfonate as a second electrolyte component to an electrolytic solution using LiPF6 as the electrolyte and incorporating these in a specific ratio in a non-aqueous electrolytic solution, the initial charge capacity, input / output characteristics, and internal impedance characteristics of the battery are improved, and an excellent battery that can be used in a wide range of applications, such as portable devices, electric vehicles, and large stationary power sources, can be provided. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2013 / 058235 [Patent Document 2] JP 2013-152956 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in response to the recent demand for improving the characteristics of non-aqueous electrolyte batteries, the above-mentioned conventional techniques have not yet achieved a high level of performance of non-aqueous electrolyte batteries. For example, the non-aqueous electrolyte battery of Patent Document 1 is required to further improve capacity and reduce internal resistance, while the non-aqueous electrolyte battery of Patent Document 2 is required to further improve durability after high-temperature storage. In particular, large batteries for automobiles are placed at high temperatures due to heat from the motor and heat from the solar heat, depending on the usage environment. Therefore, there has been a demand for a non-aqueous electrolyte battery that has improved high-temperature characteristics at high temperatures, such as a capacity retention rate, gas generation amount, and resistance increase after high-temperature storage, and is highly safe. An object of the present invention is to provide a nonaqueous electrolyte battery which is highly safe and in which the capacity loss, gas generation amount and resistance increase after high-temperature storage are small. [Means for solving the problem]

[0006] As a result of intensive research aimed at solving the above problems, the present inventors have discovered that by using a specific positive electrode and a nonaqueous electrolyte containing a specific compound to form a nonaqueous electrolyte battery, it is possible to obtain a nonaqueous electrolyte battery that has small capacity loss, small amount of gas generation, and small increase in resistance after high-temperature storage, and have arrived at the present invention. That is, the gist of the present invention is as follows. [1] A nonaqueous electrolyte solution containing a compound represented by the following formula (1) and a compound represented by the following formula (2):

[0007] [ka]

[0008] (In the above formula (1), R 1 -CHR 2 -CHR 3 -, -CHR 2 -CH2-CHR 3 -, -CHR2 -CHR 3 -CH2-, -CR 2 =CR 3 -and-CR 2 =CH-CHR 3 - is an organic group selected from the group consisting of 2 and R 3 represents a hydrogen atom, a halogen atom, or an organic group having 1 to 10 carbon atoms which are independent or bonded to each other, and a hydrogen atom bonded to a carbon atom may be substituted with a halogen atom, and may have one or more ether bonds or unsaturated bonds. M 1 -(A-SO3)x …(2) (In the above formula (2), M 1 is a metal atom, N(R 4 )4 or P(R 4 )4 (where R 4 is an organic group having 1 to 12 carbon atoms or a hydrogen atom (provided that the four R 4 cannot all be hydrogen atoms), multiple R 4 may be the same or different, and the four R 4 may form a ring together with the nitrogen atom or phosphorus atom to which they are bonded), A is a hydrogen atom, a halogen atom or an organic group having 1 to 12 carbon atoms, M 1 is a metal atom, x is the valence of the metal atom M and is an integer of 1 or more, and M 1 N(R 4 )4 or P(R 4 )If 4, then x is 1.

[0009] [2] In the formula (1), R 1 -CHR 2 -CHR 3 -OR-CR 2 =CR 3 The non-aqueous electrolyte according to [1], [3] In the formula (1), R 2 and R 3 wherein at least one of the two groups has a carbon-carbon unsaturated bond. [4] In the formula (1), R 2 and R3 The nonaqueous electrolyte according to [1] or [2], wherein the nonaqueous electrolyte does not contain a carbon-carbon unsaturated bond.

[0010] [5] The nonaqueous electrolyte solution according to any one of [1] to [4], wherein the content of the compound represented by formula (1) in the nonaqueous electrolyte solution is 0.001% by mass or more and 10.0% by mass or less. [6] The nonaqueous electrolyte solution according to any one of [1] to [5], wherein in formula (2), A is a halogen atom. [7] The nonaqueous electrolyte solution according to any one of [1] to [6], wherein the content of the compound represented by formula (2) in the nonaqueous electrolyte solution is 0.001% by mass or more and 10.0% by mass or less.

[0011] [8] The nonaqueous electrolyte solution according to any one of [1] to [7], wherein the nonaqueous electrolyte solution contains at least one selected from the group consisting of monofluorophosphates and difluorophosphates. [9] The nonaqueous electrolyte solution according to any one of [1] to [8], wherein the nonaqueous electrolyte solution contains a cyclic carbonate having a carbon-carbon unsaturated bond and / or a fluorine-containing cyclic carbonate.

[10] A nonaqueous electrolyte battery comprising: a positive electrode having a positive electrode active material capable of absorbing and releasing metal ions; a negative electrode having a negative electrode active material capable of absorbing and releasing metal ions; and the nonaqueous electrolyte according to any one of [1] to [9].

[0012]

[11] The nonaqueous electrolyte battery according to

[10] , wherein the positive electrode active material contains a lithium transition metal compound represented by the following composition formula (I): Li 1+x M 4 O2···(I) (In the above composition formula (I), x is -0.1 or more and 0.5 or less, M 4 At least Ni and Co, and Ni / M 4 The molar ratio is 0.45 or more and 1.0 or less.)

[12] The positive electrode has a plate density of 3.0 g / cm 3The nonaqueous electrolyte battery according to

[10] or

[11] above. Effect of the Invention

[0013] According to the present invention, a nonaqueous electrolyte battery can be obtained which is highly safe and which exhibits small capacity loss, small amount of gas generation, and small increase in resistance after high-temperature storage. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The following describes in detail the embodiments of the present invention. However, the following description is merely an example (representative example) of the present invention, and the present invention is not limited to the contents thereof as long as it does not depart from the gist of the claims. The embodiment of the present invention relates to a nonaqueous electrolyte and a nonaqueous electrolyte battery using the same, and the nonaqueous electrolyte battery includes a positive electrode having a positive electrode active material capable of absorbing and releasing metal ions, a negative electrode having a negative electrode active material capable of absorbing and releasing metal ions, and a nonaqueous electrolyte. Each component will be described below.

[0015] [1.Non-aqueous electrolyte] The nonaqueous electrolytic solution of the present invention, like a general nonaqueous electrolytic solution, contains an electrolyte and a nonaqueous solvent that dissolves the electrolyte, and is mainly characterized in that it contains a compound represented by the following formula (1) (hereinafter may be abbreviated as a "specific cyclic acid anhydride") and a compound represented by the following formula (2) (hereinafter may be abbreviated as a "specific sulfonic acid compound").

[0016] [ka]

[0017] In the above formula (1), R 1 -CHR 2 -CHR 3 -, -CHR 2 -CH2-CHR 3 -, -CHR 2 -CHR 3 -CH2-, -CR 2 =CR 3-and-CR 2 =CH-CHR 3 - is an organic group selected from the group consisting of 2 and R 3 represents a hydrogen atom, a halogen atom, or an organic group having 1 to 10 carbon atoms which are independent or bonded to each other, and a hydrogen atom bonded to a carbon atom may be substituted with a halogen atom, and may have one or more ether bonds or unsaturated bonds.

[0018] M 1 -(A-SO3)x …(2) In the above formula (2), M 1 is a metal atom, N(R 4 )4 or P(R 4 )4 (where R 4 is an organic group having 1 to 12 carbon atoms or a hydrogen atom (provided that the four R 4 cannot all be hydrogen atoms), multiple R 4 may be the same or different, and the four R 4 may form a ring together with the nitrogen atom or phosphorus atom to which they are bonded), A is a hydrogen atom, a halogen atom or an organic group having 1 to 12 carbon atoms, M 1 is a metal atom, x is a metal atom M 1 is an integer of 1 or more, and M 1 N(R 4 )4 or P(R 4 )4, then x is 1.

[0019] [1-1. Specific cyclic acid anhydrides] The specific cyclic acid anhydride according to the present invention is represented by the formula (1), 1 -CHR 2 -CHR 3 -, -CHR 2 -CH2-CHR 3 -, -CHR 2 -CHR 3 -CH2-, -CR 2 =CR 3 -and-CR 2 =CH-CHR 3 -, wherein R2 and R 3 represents a hydrogen atom, a halogen atom, or an organic group having 1 to 10 carbon atoms which are independent or bonded to each other, and a hydrogen atom bonded to a carbon atom may be substituted with a halogen atom, and may have one or more ether bonds or unsaturated bonds. 1 As an example, -CHR 2 -CHR 3 -, -CHR 2 -CH2-CHR 3 -, -CHR 2 -CHR 3 -CH2- or -CR 2 =CR 3 - is preferred, -CHR 2 -CHR 3 -or-CR 2 =CR 3 - is more preferred, -CHR 2 -CHR 3 - is most preferred. 2 and R 3 are preferably hydrogen atoms, halogen atoms, or organic groups each having 1 to 10 carbon atoms, more preferably hydrogen atoms or organic groups each having 1 to 10 carbon atoms, particularly preferably hydrogen atoms or organic groups each having 1 to 10 carbon atoms that do not contain a halogen atom, and most preferably hydrogen atoms. 2 and R 3 The number of carbon-carbon unsaturated bonds in R is not particularly limited, but is preferably 6 or less, more preferably 4 or less, even more preferably 2 or less, particularly preferably 1 or less, and most preferably 0. 2 and R 3 The number of carbon atoms is not particularly limited, but is preferably 6 or less, more preferably 4 or less, even more preferably 2 or less, particularly preferably 1 or less, and most preferably 0.

[0020] Preferred examples of the "specific cyclic acid anhydride" include malonic anhydride, succinic anhydride, glutaric anhydride, adipic anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, phthalic anhydride, cyclohexane-1,2-dicarboxylic anhydride, 4-cyclohexene-1,2-dicarboxylic anhydride, 3,4,5,6-tetrahydrophthalic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, methyl-5-norbornene-2,3-dicarboxylic anhydride, phenylsuccinic anhydride, 2-phenylglutaric anhydride, allylsuccinic anhydride, 3-(3-methylallyl)dihydrofuran-2,5-dione, 3-(3,3-dimethylallyl)dihydrofuran-2,5-dione, 3-(2 3-(2,3-dimethylallyl)dihydrofuran-2,5-dione, 3-(2,3,3-trimethylallyl)dihydrofuran-2,5-dione, 3-(2-propyn-1-yl)dihydrofuran-2,5-dione, 3-(1-methyl-2-propyn-1-yl)dihydrofuran-2,5-dione, 3-(1,2-dimethyl-2-propyn-1-yl)dihydrofuran-2,5-dione, 3-fluorodihydrofuran-2,5-dione, 3,4-difluorodihydrofuran-2,5-dione, 3-trifluoromethyldihydrofuran-2,5-dione, 3,3,4,4-tetrafluoro-dihydrofuran-2,5-dione, and the like.

[0021] Of these, succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, itaconic anhydride, phthalic anhydride, 3,4,5,6-tetrahydrophthalic anhydride, allylsuccinic anhydride, 3-(2-propyn-1-yl)dihydrofuran-2,5-dione, 3-(1-methyl-2-propyn-1-yl)dihydrofuran-2,5-dione and 3-(1,2-dimethyl-2-propyn-1-yl)dihydrofuran-2,5-dione are preferred, succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, itaconic anhydride, phthalic anhydride and allylsuccinic anhydride are more preferred, and succinic anhydride, maleic anhydride and allylsuccinic anhydride are most preferred.

[0022] Reasons why the above compounds are preferred include that they are easily available industrially, which reduces the production costs of the electrolyte, and that, among the "specific cyclic acid anhydrides," they are easily soluble in non-aqueous electrolytes. The specific cyclic acid anhydride may be used alone as one type, or as two or more types in any combination and in any ratio.

[0023] The content of the specific cyclic acid anhydride in the non-aqueous electrolyte of the present invention is preferably 0.001% by mass or more in total, more preferably 0.01% by mass or more, even more preferably 0.05% by mass or more, and particularly preferably 0.1% by mass or more. The upper limit is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 3% by mass or less, and most preferably 1% by mass or less. By making the content of the specific cyclic acid anhydride to be the lower limit or more, the effect of improving the capacity retention rate after storage tends to be high, and by making it to be the upper limit or less, the amount of gas generation tends to be suppressed.

[0024] [1-2. Specific sulfonic acid compounds] The specific sulfonic acid compound according to the present invention is represented by the formula (2), 1 is a metal atom, N(R 4 )4 or P(R 4 )4 (where R 4 is an organic group having 1 to 12 carbon atoms or a hydrogen atom (provided that the four R 4 cannot all be hydrogen atoms), multiple R 4 may be the same or different, and the four R 4 may form a ring together with the nitrogen atom or phosphorus atom to which they are bonded), A is a hydrogen atom, a halogen atom or an organic group having 1 to 12 carbon atoms, M 1 is a metal atom, x is a metal atom M 1 is an integer of 1 or more, and M 1 N(R 4 )4 or P(R 4 In the case of 4), x is 1. The specific sulfonic acid compounds may be used alone or in combination of two or more kinds. In formula (2), A is preferably a halogen atom. When A is an organic group having 1 to 12 carbon atoms, it preferably has 6 or less carbon atoms, more preferably 3 or less carbon atoms, and most preferably 1 or less carbon atoms.

[0025] In formula (2), M 1 When is a metal atom, x is the valence of the metal atom and is an integer of 1 or more, specifically 1, 2, or 3. Examples of the metal atom include alkali metals such as lithium, sodium, potassium, and cesium, alkaline earth metals such as magnesium and calcium, and transition metals such as iron and copper, and lithium is particularly preferred. Preferred specific sulfonic acid compounds include LiFSO3, NaFSO3, KFSO3, CsFSO3, Mg(FSO3)2, Ca(FSO3)2, Fe(FSO3)2, Cu(FSO3)2, Al(FSO3)3, LiCH3SO3, LiCF3SO3, LiC2H5SO3, LiC2F5SO3, etc. Among them, LiFSO3, NaFSO3, KFSO3, LiCH3SO3 and LiCF3SO3 are more preferred, LiFSO3 and LiCH3SO3 are particularly preferred, and LiFSO3 is most preferred from the viewpoint of solubility in the electrolyte.

[0026] Above R 4In the above, examples of the organic group having 1 to 12 carbon atoms include a linear or branched chain alkyl group, a cyclic alkyl group, an alkenyl group, an alkynyl group, an aryl group, and an aralkyl group. These groups may be substituted with a halogen atom. These groups may also contain heteroatoms such as oxygen, nitrogen, sulfur, phosphorus, and silicon, and each group may be bonded to the other groups through a saturated or unsaturated bond with these atoms. Specifically, chain alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, and sec-butyl; cyclic alkyl groups such as cyclohexyl and norbornanyl; alkenyl groups such as vinyl, 1-propenyl, allyl, butenyl, and 1,3-butadienyl; alkynyl groups such as ethynyl, propynyl, and butynyl; aryl groups such as phenyl, which may have a substituent such as an alkyl group; aralkyl groups such as benzyl and phenylethyl; halogenated alkyl groups such as trifluoromethyl, trifluoroethyl, and hexafluoropropyl; carbonyl-containing alkyl groups such as ethoxycarbonylethyl; ether-containing alkyl groups such as methoxyethyl, phenoxymethyl, ethoxyethyl, allyloxyethyl, methoxyethoxyethyl, and ethoxyethoxyethyl; and sulfonyl-containing alkyl groups such as sulfonylmethyl. Also included are trialkylsilyl groups such as trimethylsilyl. Preferably, it is a methyl group, an ethyl group, Examples of such groups include an n-propyl group, an n-butyl group, a trifluoromethyl group, a trifluoroethyl group, a methoxyethyl group, a methoxyethoxyethyl group, and a trimethylsilyl group.

[0027] N(R 4 Preferred molecular structures of 4 include quaternary ammonium cations such as tetramethylammonium, tetraethylammonium, and tetrabutylammonium; Pyrrolidinium cations represented by dimethylpyrrolidinium, methylethylpyrrolidinium, diethylpyrrolidinium, and the like; piperidinium cations represented by dimethylpiperidinium, methylethylpiperidinium, diethylpiperidinium, and the like; morpholinium cations represented by dimethylmorpholinium, methylethylmorpholinium, diethylmorpholinium, and the like; Pyridinium cations such as 1-methylpyridinium and 1-ethylpyridinium; Pyridazinium cations, such as 1-methylpyridazinium and 1-ethylpyridazinium; Pyrimidinium cations represented by 1-methylpyrimidinium, 1-ethylpyrimidinium, etc.; Pyrazinium cations, such as 1-methylpyrazinium and 1-ethylpyrazinium; Imidazolium cations such as 1,3-dimethylimidazolium, 1-ethyl-3-methylimidazolium, and 1,2,3-trimethylimidazolium; Oxazolium cations such as 1-methyloxazolium and 1-ethyloxazolium; Thiazolium cations such as 1-methylthiazolium, 1-ethylthiazolium, etc.; Pyrazolium cations such as 1-methylpyrazolium and 1-ethylpyrazolium; Examples of the triazolium cations include 1-methyltriazolium and 1-ethyltriazolium.

[0028] Preferred ammonium cation structures include tetramethylammonium, trimethylethylammonium, trimethylpropylammonium, trimethylbutylammonium, trimethylpentylammonium, trimethylhexylammonium, dimethyldiethylammonium, dimethylethylpropylammonium, dimethylethylbutylammonium, dimethylethylpentylammonium, dimethylethylhexylammonium, dimethyldipropylammonium, dimethylpropylbutylammonium, dimethylpropylpentylammonium, dimethylpropylhexylammonium, dimethyldibutylammonium, dimethylbutylpentylammonium, dimethylbutylhexylammonium, dimethyldipentylammonium, dimethylpentylhexylammonium, dimethyldihexylammonium, methyldiethylpropylammonium, methyldiethylbutylammonium, methyldiethylpentylammonium, methyldiethylhexylammonium, methylethyldipropylammonium, ammonium, methylethylpropylbutylammonium, methylethylpropylpentylammonium, methylethylpropylhexylammonium, methylethyldibutylammonium, methylethylbutylpentylammonium, methylethylbutylhexylammonium, methylethyldipentylammonium, methylethylpentylhexylammonium, methylethyldihexylammonium, methyltripropylammonium, methyldipropylbutylammonium, methyldipropylpentylammonium, methyldipropylhexylammonium, methylpropyldibutylammonium, methylpropylbutylpentylammonium, methylpropylbutylhexylammonium, methylpropyldipentylammonium, methylpropylpentylhexylammonium, methylpropyldihexylammonium, methyltributylammonium, methyldibutylpentylammonium, methyldibutylhexylammonium, methylbutyldipentylammonium, methylbutylpentylhexylammonium, Examples of such cations include methylbutyldihexylammonium, methyltripentylammonium, methyldipentylhexylammonium, methylpentyldihexylammonium, methyltrihexylammonium, triethylpropylammonium, triethylbutylammonium, triethylpentylammonium, triethylhexylammonium, and the like; and cations of compounds in which one or more hydrogen atoms in these alkyl groups have been substituted with fluorine atoms, trimethylallylammonium, trimethylbutenylammonium, trimethylmethoxymethylammonium, trimethylmethoxyethylammonium, and trimethylmethoxyethoxyethylammonium.

[0029] Preferred pyrrolidinium cation structures include dimethylpyrrolidinium, methylethylpyrrolidinium, diethylpyrrolidinium, methylpropylpyrrolidinium, ethylpropylpyrrolidinium, dipropylpyrrolidinium, methylbutylpyrrolidinium, ethylbutylpyrrolidinium, propylbutylpyrrolidinium, dibutylpyrrolidinium, or cations of compounds in which one or more hydrogen atoms in the alkyl groups are substituted with fluorine atoms, methylvinylpyrrolidinium, ethylvinylpyrrolidinium, propylvinylpyrrolidinium, butylvinylpyrrolidinium, methylallylpyrrolidinium, ethylallylpyrrolidinium, propylallylpyrrolidinium, butylallylpyrrolidinium, diallylpyrrolidinium, methylbutenylpyrrolidinium, ethylbutenylpyrrolidinium, propylbutenylpyrrolidinium, butylbutenylpyrrolidinium, dibutenylpyrrolidinium, methyl Examples of the methoxymethylpyrrolidinium include ethyl methoxymethylpyrrolidinium, methyl methoxyethylpyrrolidinium, methyl ethoxyethylpyrrolidinium, methyl methoxyethoxyethylpyrrolidinium, methyl ethoxyethoxyethylpyrrolidinium, ethyl methoxymethylpyrrolidinium, ethyl methoxyethylpyrrolidinium, ethyl ethoxyethylpyrrolidinium, ethyl methoxyethoxyethylpyrrolidinium, ethyl methoxyethoxyethylpyrrolidinium, ethyl ethoxyethoxyethylpyrrolidinium, propyl methoxymethylpyrrolidinium, propyl methoxyethylpyrrolidinium, propyl ethoxyethylpyrrolidinium, propyl methoxyethoxyethylpyrrolidinium, propyl methoxyethoxyethylpyrrolidinium, propyl methoxyethoxyethylpyrrolidinium, propyl ethoxyethoxyethylpyrrolidinium, butyl methoxymethylpyrrolidinium, butyl methoxyethylpyrrolidinium, butyl ethoxyethylpyrrolidinium, butyl methoxyethoxyethylpyrrolidinium, and butyl ethoxyethoxyethylpyrrolidinium.

[0030] Preferred piperidinium cation structures include dimethyl piperidinium, methylethyl piperidinium, diethyl piperidinium, methylpropyl piperidinium, ethylpropyl piperidinium, dipropyl piperidinium, methylbutyl piperidinium, ethylbutyl piperidinium, propylbutyl piperidinium, dibutyl piperidinium, or cations of compounds in which one or more hydrogen atoms in the alkyl groups are substituted with fluorine atoms, methylvinyl piperidinium, ethylvinyl piperidinium, propylvinyl piperidinium, butylvinyl piperidinium, methylallyl piperidinium, ethylallyl piperidinium, propylallyl piperidinium, butylallyl piperidinium, diallyl piperidinium, methylbutenyl piperidinium, ethylbutenyl piperidinium, propylbutenyl piperidinium, butylbutenyl Ru piperidinium, dibutenyl piperidinium, methyl methoxymethyl piperidinium, methyl methoxyethyl piperidinium, methyl ethoxyethyl piperidinium, methyl methoxyethoxyethyl piperidinium, methyl ethoxyethoxyethyl piperidinium, ethyl methoxymethyl piperidinium, ethyl methoxyethyl piperidinium, ethyl ethoxyethyl piperidinium, ethyl methoxyethoxyethyl piperidinium, ethyl methoxyethoxyethyl piperidinium, ethyl ethoxyethoxyethyl piperidinium, propyl methoxymethyl piperidinium, propyl methoxyethyl piperidinium, propyl ethoxyethyl piperidinium, propyl methoxyethoxyethyl piperidinium, propyl methoxyethoxyethyl piperidinium, propyl ethoxyethoxyethyl piperidinium, butyl methoxymethyl piperidinium, butyl methoxyethyl piperidinium, butyl ethoxyethyl piperidinium, butyl ethoxyethoxyethylpiperidinium, butylethoxyethoxyethylpiperidinium, and the like.

[0031] Preferred morpholinium cation structures include dimethylmorpholinium, methylethylmorpholinium, diethylmorpholinium, methylpropylmorpholinium, ethylpropylmorpholinium, dipropylmorpholinium, methylbutylmorpholinium, ethylbutylmorpholinium, propylbutylmorpholinium, dibutylmorpholinium, or cations of compounds in which one or more hydrogen atoms in the alkyl groups are substituted with fluorine atoms, methylvinylmorpholinium, ethylvinylmorpholinium, propylvinylmorpholinium, butylvinylmorpholinium, methylallylmorpholinium, ethylallylmorpholinium, propylallylmorpholinium, butylallylmorpholinium, diallylmorpholinium, methylbutenylmorpholinium, ethylbutenylmorpholinium, propylbutenylmorpholinium, butylbutenylmorpholinium, dibutenylmorpholinium, methyl Examples of the methyl methoxymethyl morpholinium include methyl methoxyethyl morpholinium, methyl ethoxyethyl morpholinium, methyl methoxyethoxyethyl morpholinium, methyl ethoxyethoxyethyl morpholinium, ethyl methoxymethyl morpholinium, ethyl methoxyethyl morpholinium, ethyl ethoxyethyl morpholinium, ethyl methoxyethoxyethyl morpholinium, ethyl ethoxyethoxyethyl morpholinium, propyl methoxymethyl morpholinium, propyl methoxyethyl morpholinium, propyl ethoxyethyl morpholinium, propyl methoxyethoxyethyl morpholinium, propyl methoxyethoxyethyl morpholinium, propyl ethoxyethoxyethyl morpholinium, butyl methoxymethyl morpholinium, butyl methoxyethyl morpholinium, butyl ethoxyethyl morpholinium, butyl methoxyethoxyethyl morpholinium, and butyl ethoxyethoxyethyl morpholinium.

[0032] Preferred pyridinium cation structures include 1-ethylpyridinium, 1-propylpyridinium, 1-butylpyridinium, 1-pentylpyridinium, 1-hexylpyridinium, 1-allylpyridinium, 1-butenylpyridinium, 1-methoxymethylpyridinium, and 1-methoxyethylpyridinium. Preferred pyridazinium cation structures include 1-ethylpyridazinium, 1-propylpyridazinium, 1-butylpyridazinium, 1-pentylpyridazinium, 1-hexylpyridazinium, 1-allylpyridazinium, 1-butenylpyridazinium, 1-methoxymethylpyridazinium, and 1-methoxyethylpyridazinium.

[0033] Preferred pyrimidinium cation structures include 1-ethylpyrimidinium, 1-propylpyrimidinium, 1-butylpyrimidinium, 1-pentylpyrimidinium, 1-hexylpyrimidinium, 1-allylpyrimidinium, 1-butenylpyrimidinium, 1-methoxymethylpyrimidinium, and 1-methoxyethylpyrimidinium. Preferred pyrazinium cation structures include 1-ethylpyrazinium, 1-propylpyrazinium, 1-butylpyrazinium, 1-pentylpyrazinium, 1-hexylpyrazinium, 1-allylpyrazinium, 1-butenylpyrazinium, 1-methoxymethylpyrazinium, and 1-methoxyethylpyrazinium.

[0034] Preferred imidazolium cation structures include 1,3-dimethylimidazolium, 1-ethyl-3-methylimidazolium, 1-propyl-3-methylimidazolium, 1-butyl-3-methylimidazolium, 1-pentyl-3-methylimidazolium, 1-hexyl-3-methylimidazolium, 1,3-diethylimidazolium, 1-ethyl-3-propylimidazolium, 1-ethyl-3-butylimidazolium, 1-ethyl-3-pentylimidazolium, 1-ethyl-3-hexylimidazolium, 1,3-dipropylimidazolium, 1-propyl-3-butylimidazolium, 1-propyl-3-pentylimidazolium, 1-ethyl-3-hexylimidazolium, 1,3-dipropylimidazolium, 1-propyl-3-butylimidazolium, 1-propyl-3-pentylimidazolium, 1-ethyl-3-hexylimidazolium, 1,3-dipropylimidazolium, 1-propyl-3-butylimidazolium, 1-propyl-3-pentylimidazolium, 1-ethyl-3-pentylimidazolium, 1-ethyl-3-hexylimidazolium, 1,3-dipropylimidazolium, 1-propyl-3-pentylimidazolium, 1-propyl-3-pentylimidazolium, 1-ethyl ... 1-Hexyl-3-butylimidazolium, 1,2,3-trimethylimidazolium, 1-ethyl-2,3-dimethylimidazolium, 1-propyl-2,3-dimethylimidazolium, 1-butyl-2,3-dimethylimidazolium, 1-pentyl-2,3-dimethylimidazolium, 1-hexyl-2,3-dimethylimidazolium, 1,3-diethyl-2-methylimidazolium, 1-propyl-2-methyl-3-ethylimidazolium, 1-butyl-2-methyl-3 -Ethylimidazolium, 1-pentyl-2-methyl-3-ethylimidazolium, 1-hexyl-2-methyl-3-ethylimidazolium, 1,2,3,4,5-hexamethylimidazolium, 1-ethyl-2,3,4,5-tetramethylimidazolium, 1-propyl-2,3,4,5-tetramethylimidazolium, 1-butyl-2,3,4,5-tetramethylimidazolium, 1-pentyl-2,3,4,5-tetramethylimidazolium, 1-hexyl-2,3,4,5-tetramethyl imidazolium or a cation of a compound in which one or more hydrogen atoms in the alkyl group of these imidazoliums have been substituted with a fluorine atom, 1-allyl-3-methylimidazolium, 1-allyl-3-ethylimidazolium, 1-allyl-3-propylimidazolium, 1-allyl-3-butylimidazolium, 1-allyl-2,3-dimethylimidazolium, 1-allyl-2,3,4,5-tetramethylimidazolium, 1-butenyl-3-methylimidazolium, 1-butenyl-3-ethylimidazolium, 1-butenyl 1-propyl-3-propylimidazolium, 1-butenyl-3-butylimidazolium, 1-butenyl-2,3-dimethylimidazolium, 1-butenyl-2,3,4,5-tetramethylimidazolium, 1-methoxymethyl-3-methylimidazolium, 1-methoxymethyl-3-ethylimidazolium, 1-methoxymethyl-3-propylimidazolium, 1-methoxymethyl-3-butylimidazolium, 1-methoxymethyl-2,3-dimethylimidazolium, 1-methoxymethyl-2,3,4,Examples of the imidazolium include 5-tetramethylimidazolium, 1-methoxyethyl-3-methylimidazolium, 1-methoxyethyl-3-ethylimidazolium, 1-methoxyethyl-3-propylimidazolium, 1-methoxyethyl-3-butylimidazolium, 1-methoxyethyl-2,3-dimethylimidazolium, and 1-methoxyethyl-2,3,4,5-tetramethylimidazolium.

[0035] Preferred oxazolium cation structures include 1-ethyloxazolium, 1-propyloxazolium, 1-butyloxazolium, 1-pentyloxazolium, 1-hexyloxazolium, 1-allyloxazolium, 1-butenyloxazolium, 1-methoxymethyloxazolium, 1-methoxyethyloxazolium, 1-ethyl-2,4,5-trimethyloxazolium, 1-propyl-2,4,5-trimethyloxazolium, 1-butyl-2,4,5-trimethyloxazolium, 1-pentyl-2,4,5-trimethyloxazolium, 1-hexyl-2,4,5-trimethyloxazolium, 1-allyl-2,4,5-trimethyloxazolium, 1-butenyl-2,4,5-trimethyloxazolium, 1-methoxymethyl-2,4,5-trimethyloxazolium, and 1-methoxyethyl-2,4,5-trimethyloxazolium.

[0036] Preferred thiazolium cation structures include 1-ethylthiazolium, 1-propylthiazolium, 1-butylthiazolium, 1-pentylthiazolium, 1-hexylthiazolium, 1-allylthiazolium, 1-butenylthiazolium, 1-methoxymethylthiazolium, 1-methoxyethylthiazolium, 1-ethyl-2,4,5-trimethylthiazolium, 1-propyl-2,4,5-trimethylthiazolium, 1-butyl-2,4,5-trimethylthiazolium, 1-pentyl-2,4,5-trimethylthiazolium, 1-hexyl-2,4,5-trimethylthiazolium, 1-allyl-2,4,5-trimethylthiazolium, 1-butenyl-2,4,5-trimethylthiazolium, 1-methoxymethyl-2,4,5-trimethylthiazolium, and 1-methoxyethyl-2,4,5-trimethylthiazolium.

[0037] Preferred pyrazolium cation structures include 1-ethylpyrazolium, 1-propylpyrazolium, 1-butylpyrazolium, 1-pentylpyrazolium, 1-hexylpyrazolium, 1-allylpyrazolium, 1-butenylpyrazolium, 1-methoxymethylpyrazolium, 1-methoxyethylpyrazolium, 1-ethyl-2,3,4,5-tetramethylpyrazolium, 1-propyl-2,3,4,5-tetramethylpyrazolium, 1-butyl- Examples of the pyrazolium include 2,3,4,5-tetramethylpyrazolium, 1-pentyl-2,3,4,5-tetramethylpyrazolium, 1-hexyl-2,3,4,5-tetramethylpyrazolium, 1-allyl-2,3,4,5-tetramethylpyrazolium, 1-butenyl-2,3,4,5-tetramethylpyrazolium, 1-methoxymethyl-2,3,4,5-tetramethylpyrazolium, and 1-methoxyethyl-2,3,4,5-tetramethylpyrazolium.

[0038] Preferred triazolium cation structures include 1-ethyltriazolium, 1-propyltriazolium, 1-butyltriazolium, 1-pentyltriazolium, 1-hexyltriazolium, 1-allyltriazolium, 1-butenyltriazolium, 1-methoxymethyltriazolium, 1-methoxyethyltriazolium, 1-ethyl-2,3,4,5-tetramethyltriazolium, 1-propyl-2,3,4,5-tetramethyltriazolium, 1-butenyl ... 1-pentyl-2,3,4,5-tetramethyltriazolium, 1-hexyl-2,3,4,5-tetramethyltriazolium, 1-allyl-2,3,4,5-tetramethyltriazolium, 1-butenyl-2,3,4,5-tetramethyltriazolium, 1-methoxymethyl-2,3,4,5-tetramethyltriazolium, and 1-methoxyethyl-2,3,4,5-tetramethyltriazolium.

[0039] These N(R 4 Among the specific sulfonic acid compounds having 4 as a cation structure, tetramethylammonium fluorosulfonate, tetraethylammonium fluorosulfonate, tetrabutylammonium fluorosulfonate, dimethylpyrrolidinium fluorosulfonate, methylethylpyrrolidinium fluorosulfonate, diethylpyrrolidinium fluorosulfonate, dimethylpiperidinium fluorosulfonate, methylethylpiperidinium fluorosulfonate, diethylpiperidinium fluorosulfonate, dimethylmorpholinium fluorosulfonate, methylethylmorpholinium fluorosulfonate, diethylmorpholinium fluorosulfonate, tetramethylammonium methylsulfonate, and tetramethylammonium trifluoromethylsulfonate are particularly preferred in terms of availability and ease of handling, and in terms of reducing the internal impedance of the battery and improving the input / output characteristics.

[0040] P(R 4Preferred cationic structures of 4 include triethylbutylphosphonium, triethylpentylphosphonium, triethylhexylphosphonium, triethylheptylphosphonium, triethyloctylphosphonium, diethylpropylbutylphosphonium, diethylpropylpentylphosphonium, diethylpropylhexylphosphonium, diethylpropylheptylphosphonium, diethylpropyloctylphosphonium, diethylbutylpentylphosphonium, diethylbutylhexylphosphonium, diethylbutylheptylphosphonium, diethylbutyloctylphosphonium, diethylpentylhexylphosphonium, diethylpentylheptylphosphonium, diethylpentylheptylphosphonium, nium, diethylpentyl octyl phosphonium, diethylhexylheptyl phosphonium, diethylhexyl octyl phosphonium, diethylheptyl octyl phosphonium, diethyldioctyl phosphonium, ethyldipropyl butyl phosphonium, ethyldipropyl pentyl phosphonium, ethyldipropyl hexyl phosphonium, ethyldipropyl heptyl phosphonium, ethyldipropyl octyl phosphonium, ethylpropyl dibutyl phosphonium, ethylpropyl butyl pentyl phosphonium, ethylpropyl butyl hexyl phosphonium, ethylpropyl butyl heptyl phosphonium, ethylpropyl butyl octyl phosphonium, ethylpropyl ethyl dipentyl phosphonium, ethyl propyl pentyl hexyl phosphonium, ethyl propyl pentyl heptyl phosphonium, ethyl propyl pentyl octyl phosphonium, ethyl propyl dihexyl phosphonium, ethyl propyl hexyl heptyl phosphonium, ethyl propyl hexyl octyl phosphonium, ethyl propyl diheptyl phosphonium, ethyl propyl heptyl octyl phosphonium, ethyl propyl dioctyl phosphonium, ethyl tributyl phosphonium, ethyl dibutyl pentyl phosphonium, ethyl dibutyl hexyl phosphonium, ethyl dibutyl heptyl phosphonium, ethyl dibutyl octyl phosphonium, ethyl butyl dipentyl phosphonium, ethyl butyl pentyl hexyl phosphonium, ethyl butyl pentyl heptyl phosphonium, ethyl butyl pentyl octyl phosphonium, ethyl butyl dihexyl phosphonium, ethyl butyl hexyl heptyl phosphonium, ethyl butyl hexyl octyl phosphonium, ethyl butyl heptyl octyl phosphonium, ethyl butyl dioctyl phosphonium, ethyl tripentyl phosphonium, ethyl dipentyl Hexyl phosphonium, ethyl dipentylheptyl phosphonium, ethyl dipentyl octyl phosphonium, ethyl pentyl dihexyl phosphonium, ethyl pentyl hexylheptyl phosphonium, ethyl pentyl hexyl octyl phosphonium, ethyl pentyl diheptyl phosphonium, ethyl pentyl heptyl octyl phosphonium, ethyl pentyl dioctyl phosphonium, ethyl trihexyl phosphonium, ethyl dihexylheptyl phosphonium, ethyl dihexyl octyl phosphonium, ethyl hexyl diheptyl phosphonium, ethylhexylheptyloctyl phosphonium, ethylhexyldioctyl phosphonium, ethyltriheptyl phosphonium, ethyldiheptyloctyl phosphonium, ethylheptyldioctyl phosphonium, ethyltrioctyl phosphonium, tripropylbutyl phosphonium, tripropylpentyl phosphonium, tripropylhexyl phosphonium, tripropylheptyl phosphonium, tripropyloctyl phosphonium, dipropyldibutyl phosphonium, dipropylbutylpentyl phosphonium, dipropylbutylhexyl phosphonium,dipropyl butylheptyl phosphonium, dipropyl butyl octyl phosphonium, dipropyl dipentyl phosphonium, dipropyl pentyl hexyl phosphonium, dipropyl pentyl heptyl phosphonium, dipropyl pentyl octyl phosphonium, dipropyl dihexyl phosphonium, dipropyl hexyl heptyl phosphonium, dipropyl hexyl octyl phosphonium, dipropyl diheptyl phosphonium, dipropyl heptyl octyl phosphonium, dipropyl dioctyl phosphonium, propyl tributyl phosphonium, propyl dibutyl pentyl phosphonium, propyl dibutyl hexyl phosphonium, propyl dibutyl heptyl phosphonium, propyl dibutyl octyl phosphonium, propyl butyl dipentyl phosphonium, propyl butyl pentyl hexyl phosphonium, propyl butyl pentyl heptyl phosphonium, propyl butyl pentyl octyl phosphonium, propyl butyl diheptyl phosphonium, propyl butyl heptyl octyl phosphonium, propyl butyl dioctyl phosphonium, propyl tripentyl phosphonium, propyl dipentyl hexyl phosphonium, propyl dipentylheptyl phosphonium, propyl dipentyl heptyl octyl phosphonium, propyl pentyl hexyl heptyl phosphonium, propyl pentyl hexyl octyl phosphonium, propyl pentyl diheptyl phosphonium, propyl pentyl heptyl octyl phosphonium, propyl pentyl dioctyl phosphonium, propyl trihexyl phosphonium, propyl dihexyl heptyl phosphonium, propyl dihexyl octyl phosphonium, propyl hexyl diheptyl phosphonium, propyl hexyl heptyl octyl phosphonium, propylhexyl dioctyl phosphonium, propyl triheptyl phosphonium, propyl diheptyl octyl phosphonium, propyl heptyl dioctyl phosphonium, propyl trioctyl phosphonium, tetrabutyl phosphonium, tributyl pentyl phosphonium, tributyl hexyl phosphonium, tributyl heptyl phosphonium, tributyl octyl phosphonium, tetrapentyl phosphonium, tripentyl hexyl phosphonium, tripentyl heptyl phosphonium, tripentyl octyl phosphonium, tetrahexyl phosphonium,Trihexylheptylphospho, cations of compounds in which one or more hydrogen atoms in these alkyl groups have been substituted with fluorine atoms; triethylallylphosphonium, triethylbutenylphosphonium, tripropylallylphosphonium, tripropylbutenylphosphonium, tributylallylphosphonium, tributylbutenylphosphonium, triethylmethoxyethylphosphonium, triethylmethoxyethoxyethylphosphonium, tripropylmethoxyethylphosphonium, tripropylmethoxyethoxyethylphosphonium, tributylmethoxyethylphosphonium, tributylmethoxyethoxyethylphosphonium, and the like.

[0041] These P(R 4 Among the specific sulfonic acid compounds having 4 as a cationic structure, tetramethylphosphonium fluorosulfonate, tetraethylphosphonium fluorosulfonate, tetrabutylphosphonium fluorosulfonate, tetramethylphosphonium methylsulfonate, and tetramethylphosphonium trifluoromethylsulfonate are particularly preferred in terms of availability and ease of handling.

[0042] In the non-aqueous electrolyte of the present invention, the specific sulfonic acid compound may be at least one kind, and may be used alone or in combination of two or more kinds. When two or more kinds are used, it is preferable that one of them is LiFSO3. In particular, a combination of LiFSO3 with one or more selected from NaFSO3, KFSO3, tetraalkylammonium fluorosulfonate (e.g., methylammonium, tetraethylammonium fluorosulfonate, tetrabutylammonium fluorosulfonate), dimethylpyrrolidinium fluorosulfonate, methylethylpyrrolidinium fluorosulfonate, diethylpyrrolidinium fluorosulfonate, dimethylpiperidinium fluorosulfonate, methylethylpiperidinium fluorosulfonate, diethylpiperidinium fluorosulfonate, dimethylmorpholinium fluorosulfonate, methylethylmorpholinium fluorosulfonate, diethylmorpholinium fluorosulfonate, tetramethylphosphonium fluorosulfonate, tetraethylphosphonium fluorosulfonate, tetrabutylphosphonium fluorosulfonate, lithium methylsulfonate, and lithium trifluoromethylsulfonate is preferred.

[0043] Specifically, LiFSO3 and NaFSO3, LiFSO3 and KFSO3, LiFSO3 and tetramethylammonium fluorosulfonate, LiFSO3 and tetraethylammonium fluorosulfonate, LiFSO3 and tetrabutylammonium fluorosulfonate, LiFSO3 and dimethylpyrrolidinium fluorosulfonate, LiFSO3 and methylethylpyrrolidinium fluorosulfonate, LiFSO3 and diethylpyrrolidinium fluorosulfonate, LiFSO3 and dimethylpiperidinium fluorosulfonate, LiFSO3 and methylethylpiperidinium fluorosulfonate, LiFSO3 and fluorosulfonate. Combinations of LiFSO3 and diethylpiperidinium fluorosulfonate, LiFSO3 and dimethylmorpholinium fluorosulfonate, LiFSO3 and methylethylmorpholinium fluorosulfonate, LiFSO3 and diethylmorpholinium fluorosulfonate, LiFSO3 and tetramethylphosphonium fluorosulfonate, LiFSO3 and tetraethylphosphonium fluorosulfonate, LiFSO3 and tetrabutylphosphonium fluorosulfonate, LiFSO3 and lithium methylsulfonate, and LiFSO3 and lithium trifluoromethylsulfonate are preferred in terms of increasing the lithium concentration in the non-aqueous electrolyte.

[0044] The content of the specific sulfonic acid compound in the non-aqueous electrolyte of the present invention is preferably 0.001% by mass or more in total, more preferably 0.01% by mass or more, even more preferably 0.05% by mass or more, and particularly preferably 0.1% by mass or more. The upper limit is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less. By setting the content of the phononate compound to be equal to or more than the above lower limit, the effect of improving the capacity retention rate after storage tends to be greater, and by setting it to be equal to or less than the above upper limit, the amount of gas generation tends to be suppressed.

[0045] The mass ratio of the specific acid anhydride and the specific sulfonic acid compound in the non-aqueous electrolyte of the present invention is not particularly limited, but the "mass of the specific acid anhydride compound / mass of the specific sulfonic acid compound" is usually 0.01 or more, preferably 0.05 or more, more preferably 0.10 or more, even more preferably 0.20, particularly preferably 0.50 or more, most preferably 1 or more, and usually 100 or less, preferably 50 or less, more preferably 10 or less, even more preferably 5 or less, particularly preferably 2 or less. Within this range, the effect of improving the capacity retention rate after storage is high, and the amount of gas generation tends to be suppressed. Although the principle behind this is unclear, it is thought that by mixing at this ratio, the side reaction of the additive on the electrode can be minimized.

[0046] [1-2. Electrolytes] There is no limitation on the electrolyte used in the non-aqueous electrolyte of the present invention, and any known electrolyte that can be used as an electrolyte in a non-aqueous electrolyte battery can be used. Usually, a lithium salt is used as the electrolyte. Specific examples of the electrolyte include: Inorganic lithium salts such as LiClO4, LiAsF6, LiPF6, LiBF4, LiSbF6, LiSO3F, LiN(FSO2)2; Fluorine-containing organic lithium salts such as LiCF3SO3, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, lithium cyclic 1,3-hexafluoropropane disulfonylimide, lithium cyclic 1,2-tetrafluoroethane disulfonylimide, LiN(CF3SO2)(C4F9SO2), LiC(CF3SO2)3, LiPF4(CF3)2, LiPF4(C2F5)2, LiPF4(CF3SO2)2, LiPF4(C2F5SO2)2, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, and LiBF2(C2F5SO2)2; dicarboxylic acid-containing complex lithium salts, such as lithium bis(oxalato)borate, lithium difluorooxalatoborate, lithium tris(oxalato)phosphate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate; etc.

[0047] Among these, from the viewpoints of solubility and degree of dissociation in non-aqueous solvents, electrical conductivity, and obtainable battery characteristics, LiPF6, LiBF4, LiSO3F, LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, lithium bis(oxalato)borate, lithium difluorooxalatoborate, lithium tris(oxalato)phosphate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate are preferred, with LiPF6 and LiBF4 being particularly preferred.

[0048] In the present invention, LiBF4, LiSO3F, lithium difluorooxalatoborate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate include those produced in nonaqueous electrolytes and nonaqueous electrolyte batteries. The electrolytes may be used alone or in any combination and ratio of two or more. Among them, the use of two specific inorganic lithium salts in combination, or the use of an inorganic lithium salt in combination with a fluorine-containing organic lithium salt, is preferable because it suppresses gas generation during trickle charging and deterioration after high-temperature storage. In particular, the use of LiPF6 in combination with LiBF4, or the use of an inorganic lithium salt such as LiPF6 or LiBF4 in combination with a fluorine-containing organic lithium salt such as LiN(FSO2)2, LiN(CF3SO2)2, or LiN(C2F5SO2)2 is preferable. It is preferable to use them in combination.

[0049] Furthermore, when LiPF6 and LiBF4 are used in combination, it is preferable that LiBF4 is contained in a ratio of 0.01 mass% or more and 50 mass% or less with respect to the entire electrolyte. The above ratio is more preferably 0.05 mass% or more, and particularly preferably 0.1 mass% or more. On the other hand, the upper limit is more preferably 20 mass% or less, even more preferably 10 mass% or less, particularly preferably 5 mass% or less, and most preferably 3 mass% or less. By having the ratio in the above range, it becomes easier to obtain the desired effect, and also, due to the low dissociation degree of LiBF4, it becomes easier to suppress the resistance of the electrolyte from increasing.

[0050] On the other hand, inorganic lithium salts such as LiPF6 and LiBF4, inorganic lithium salts such as LiSO3F and LiN(FSO2)2, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, lithium cyclic 1,3-hexafluoropropane disulfonylimide, lithium cyclic 1,2-tetrafluoroethane disulfonylimide, LiN(CF3SO2)(C4F9SO2), LiC(CF3SO2)3, LiPF4(CF3)2, LiPF4(C2F5)2, LiPF4(CF3SO2)2, LiPF4(C2F5SO2)2, LiBF2(CF3)2, LiBF2(C2F5) 2. When using in combination with fluorine-containing organic lithium salts such as LiBF2(CF3SO2)2 and LiBF2(C2F5SO2)2, or dicarboxylic acid-containing complex lithium salts such as lithium bis(oxalato)borate, lithium tris(oxalato)phosphate, lithium difluorooxalatoborate, lithium tri(oxalato)phosphate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate, the proportion of inorganic lithium salts in the entire electrolyte is usually 70% by mass or more, preferably 80% by mass or more, and more preferably 85% by mass or more. Also, it is usually 99% by mass or less, and preferably 95% by mass or less.

[0051] The content of the electrolyte in the non-aqueous electrolyte is arbitrary as long as it does not impair the gist of the present invention, but is usually 0.5 mol / L or more, preferably 0.6 mol / L or more, more preferably 0.8 mol / L or more. Also, it is usually 3 mol / L or less, preferably 2 mol / L or less, more preferably 1.8 mol / L or less, and even more preferably 1.6 mol / L or less. By the content of the electrolyte being in the above range, the electrical conductivity of the non-aqueous electrolyte becomes sufficient, and the decrease in electrical conductivity due to the increase in viscosity, i.e., the decrease in the performance of the non-aqueous electrolyte battery, is suppressed.

[0052] [1-3. Nonaqueous solvents] The non-aqueous solvent contained in the non-aqueous electrolyte solution according to the present invention can be appropriately selected from those known as solvents for non-aqueous electrolyte solutions. Examples of commonly used non-aqueous solvents include cyclic carbonates, chain carbonates, chain and cyclic carboxylates, chain ethers, phosphorus-containing organic solvents, sulfur-containing organic solvents, and aromatic fluorine-containing solvents.

[0053] Examples of cyclic carbonates include ethylene carbonate, propylene carbonate, butylene carbonate, etc. The number of carbon atoms in the cyclic carbonate is usually 3 or more and 6 or less. Among these, ethylene carbonate and propylene carbonate are preferable because they have a high dielectric constant, which makes it easy for the electrolyte to dissolve therein, and they have good cycle characteristics when used in a non-aqueous electrolyte battery.

[0054] Examples of the chain carbonate include dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl-n-propyl carbonate, ethyl-n-propyl carbonate, di-n-propyl carbonate, etc. The number of carbon atoms in the alkyl group constituting the chain carbonate is preferably 1 or more and 5 or less, and particularly preferably 1 or more and 4 or less. Among these, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate are preferable from the viewpoint of improving the battery characteristics.

[0055] In addition, chain carbonates in which a part of the hydrogen of an alkyl group is substituted with fluorine can also be mentioned. Examples of the chain carbonate substituted with fluorine include bis(fluoromethyl)carbonate, bis(difluoromethyl)carbonate, bis(trifluoromethyl)carbonate, bis(2-fluoroethyl)carbonate, bis(2,2-difluoroethyl)carbonate, bis(2,2,2-trifluoroethyl)carbonate, 2-fluoroethylmethylcarbonate, 2,2-difluoroethylmethylcarbonate, and 2,2,2-trifluoroethylmethylcarbonate.

[0056] Examples of the chain carboxylate include methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, sec-butyl acetate, isobutyl acetate, t-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, isopropyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, methyl isobutyrate, ethyl isobutyrate, methyl valerate, ethyl valerate, methyl pivalate, ethyl pivalate, etc., and chain carboxylates in which a portion of the hydrogen of these compounds is substituted with fluorine. Examples of the chain carboxylate substituted with fluorine include methyl trifluoroacetate, ethyl trifluoroacetate, propyl trifluoroacetate, butyl trifluoroacetate, 2,2,2-trifluoroethyl trifluoroacetate, etc.

[0057] Among these, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, methyl valerate, methyl isobutyrate, ethyl isobutyrate, and methyl pivalate are preferred from the viewpoint of improving battery characteristics. Examples of the cyclic carboxylate include γ-butyrolactone, γ-valerolactone, and cyclic carboxylates in which some of the hydrogen atoms in these compounds are substituted with fluorine.

[0058] Among these, γ-butyrolactone is more preferable. Examples of chain ethers include dimethoxymethane, 1,1-dimethoxyethane, 1,2-dimethoxyethane, diethoxymethane, 1,1-diethoxyethane, 1,2-diethoxyethane, ethoxymethoxymethane, 1,1-ethoxymethoxyethane, 1,2-ethoxymethoxyethane, and chain ethers in which some of the hydrogen atoms in these compounds have been replaced with fluorine.

[0059] Examples of the chain ether substituted with fluorine include bis(trifluoroethoxy)ethane, ethoxytrifluoroethoxyethane, methoxytrifluoroethoxyethane, 1,1,1,2,2,3,4,5,5,5-decafluoro-3-methoxy-4-trifluoromethyl-pentane, 1,1,1,2,2,3,4,5,5,5-decafluoro-3-ethoxy-4-trifluoromethyl-pentane, 1,1,1,2,2,3,4,5,5,5-decafluoro-3-propoxy-4-trifluoromethyl-pentane, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and 2,2-difluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0060] Among these, 1,2-dimethoxyethane and 1,2-diethoxyethane are more preferable. Examples of phosphorus-containing organic solvents include trimethyl phosphate, triethyl phosphate, dimethylethyl phosphate, methyl diethyl phosphate, ethylene methyl phosphate, ethylene ethyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, triphenyl phosphite, trimethylphosphine oxide, triethylphosphine oxide, and triphenylphosphine oxide. Examples of phosphorus-containing organic solvents include those in which hydrogen atoms of these compounds are partially substituted with fluorine atoms. Examples of phosphorus-containing organic solvents substituted with fluorine atoms include tris(2,2,2-trifluoroethyl) phosphate and tris(2,2,3,3,3-pentafluoropropyl) phosphate.

[0061] Examples of sulfur-containing organic solvents include sulfolane, 2-methylsulfolane, 3-methylsulfolane, dimethylsulfone, diethylsulfone, ethylmethylsulfone, methylpropylsulfone, dimethylsulfoxide, methyl methanesulfonate, ethyl methanesulfonate, methyl ethanesulfonate, ethyl ethanesulfonate, dimethyl sulfate, diethyl sulfate, dibutyl sulfate, and the like, as well as sulfur-containing organic solvents in which part of the hydrogen in these compounds has been substituted with fluorine.

[0062] Examples of the aromatic fluorine-containing solvent include fluorobenzene, difluorobenzene, trifluorobenzene, tetrafluorobenzene, pentafluorobenzene, hexafluorobenzene, and benzotrifluoride. Among the above non-aqueous solvents, it is preferable to use cyclic carbonates such as ethylene carbonate and / or propylene carbonate, and it is further preferable to use these in combination with a chain carbonate, since this allows the electrolyte to have both high conductivity and low viscosity.

[0063] The non-aqueous solvent may be used alone or in any combination and ratio of two or more. When two or more are used in combination, for example, when a cyclic carbonate and a chain carbonate are used in combination, the suitable content of the chain carbonate in the non-aqueous solvent is usually 20% by volume or more, preferably 40% by volume or more, and usually 95% by volume or less, preferably 90% by volume or less. On the other hand, the suitable content of the cyclic carbonate in the non-aqueous solvent is usually 5% by volume or more, preferably 10% by volume or more, and usually 80% by volume or less, preferably 60% by volume or less. By having the proportion of the chain carbonate in the above range, the increase in viscosity of the non-aqueous electrolyte solution is suppressed, and the decrease in the electrical conductivity of the non-aqueous electrolyte solution due to the decrease in the degree of dissociation of the lithium salt, which is the electrolyte, is suppressed. In this specification, the volume of the non-aqueous solvent is measured at 25°C, but for those that are solid at 25°C, such as ethylene carbonate, the measured value at the melting point is used.

[0064] [1-4. Other additives] Various additives may be contained within the range that does not significantly impair the effects of the present invention. Any additives known in the art may be used as the additives. The additives may be used alone or in any combination and ratio of two or more. The mass ratio of the specific acid anhydride and the specific sulfonic acid compound to the other additives in the nonaqueous electrolyte of the present invention is not particularly limited, but "(mass of the specific acid anhydride + the specific sulfonic acid compound) / the total mass of the other additives" is usually 0.01 or more, preferably 0.05 or more, more preferably 0.10 or more, even more preferably 0.20, particularly preferably 0.50 or more, most preferably 1 or more, and usually 100 or less, preferably 50 or less, more preferably 10 or less, even more preferably 5 or less, particularly preferably 3 or less. Within this range, the battery characteristics, particularly the capacity, capacity recovery rate and capacity maintenance rate after high-temperature storage can be increased, and the amount of gas generation can be reduced. Although the principle behind this is unclear, it is believed that by mixing at this ratio, the electrode protection action of the specific acid anhydride and the specific sulfonic acid compound functions sufficiently, and the side reaction of the additives on the electrode can be minimized.

[0065] Examples of conventionally known additives that can be added to the nonaqueous electrolyte solution of the present invention include cyclic carbonates having a carbon-carbon unsaturated bond, fluorine-containing cyclic carbonates, compounds having an isocyanato group (isocyanate group), sulfur-containing organic compounds, phosphorus-containing organic compounds, organic compounds having a cyano group, silicon-containing compounds, aromatic compounds, fluorine-free carboxylic acid esters, cyclic compounds having a plurality of ether bonds, compounds having an isocyanuric acid skeleton, monofluorophosphates, difluorophosphates, borates, oxalates, fluorosulfonates, and the like. Each additive will be described below, but some of these may include those already mentioned above.

[0066] [1-4-1. Cyclic carbonates having carbon-carbon unsaturated bonds] The cyclic carbonate having a carbon-carbon unsaturated bond (hereinafter, sometimes referred to as "unsaturated cyclic carbonate") is not particularly limited, and any unsaturated carbonate can be used as long as it is a cyclic carbonate having a carbon-carbon double bond or a carbon-carbon triple bond. Note that cyclic carbonates having an aromatic ring are also included in the unsaturated cyclic carbonate.

[0067] Examples of the unsaturated cyclic carbonate include vinylene carbonates, ethylene carbonates substituted with a substituent having an aromatic ring or a carbon-carbon double bond or a carbon-carbon triple bond, phenyl carbonates, vinyl carbonates, allyl carbonates, and catechol carbonates. Among these, particularly preferred unsaturated cyclic carbonates for use in combination include vinylene carbonate, methylvinylene carbonate, 4,5-dimethylvinylene carbonate, vinylvinylene carbonate, 4,5-vinylvinylene carbonate, allylvinylene carbonate, 4,5-diallylvinylene carbonate, vinylethylene carbonate, 4,5-divinylethylene carbonate, 4-methyl-5-vinylethylene carbonate, allylethylene carbonate, 4,5-diallylethylene carbonate, 4-methyl-5-allylethylene carbonate, 4-allyl-5-vinylethylene carbonate, ethynylethylene carbonate, 4,5-diethynylethylene carbonate, 4-methyl-5-ethynylethylene carbonate, and 4-vinyl-5-ethynylethylene carbonate. Furthermore, vinylene carbonate, vinyl ethylene carbonate, and ethynyl ethylene carbonate are preferred since they form a more stable interface protective film, with vinylene carbonate and vinyl ethylene carbonate being more preferred, and vinylene carbonate being even more preferred.

[0068] The molecular weight of the unsaturated cyclic carbonate is not particularly limited, and may be any as long as it does not significantly impair the effects of the present invention.The molecular weight is preferably 80 or more, more preferably 85 or more, and is preferably 250 or less, more preferably 150 or less.Within this range, the solubility of the unsaturated cyclic carbonate in the non-aqueous electrolyte is easily ensured, and the effects of the present invention are easily exhibited.

[0069] The method for producing the unsaturated cyclic carbonate is not particularly limited, and any known method can be selected for production. The unsaturated cyclic carbonate may be used alone or in any combination and ratio of two or more. The content of the unsaturated cyclic carbonate is not particularly limited and may be any content as long as it does not significantly impair the effects of the present invention. The content of the unsaturated cyclic carbonate is usually 0.001% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.5% by mass or more, based on 100% by mass of the non-aqueous electrolyte solution. In addition, it is usually 10% by mass or less, preferably 5% by mass or less, more preferably 4% by mass or less, further preferably 3% by mass or less, and particularly preferably 2% by mass or less. Within this range, the nonaqueous electrolyte battery is likely to exhibit a sufficient effect of improving cycle characteristics, and also has good high-temperature storage characteristics, a small amount of gas generation, and a good discharge capacity retention rate.

[0070] [1-4-2. Fluorine-containing cyclic carbonates] Examples of fluorine-containing cyclic carbonates include fluorinated cyclic carbonates having an alkylene group usually having 2 to 6 carbon atoms, and derivatives thereof. For example, fluorinated ethylene carbonate (hereinafter, sometimes referred to as "fluorinated ethylene carbonate") and derivatives thereof can be mentioned. Derivatives of fluorinated ethylene carbonate include carbon. Examples of the fluorinated ethylene carbonate include fluorinated ethylene carbonate substituted with an alkyl group having a prime number of 1 to 4. Among these, fluorinated ethylene carbonate having a fluorine number of 1 to 8 and its derivatives are preferred.

[0071] By adding a fluorine-containing cyclic carbonate, the high-temperature storage characteristics and cycle characteristics of a battery using this electrolyte can be improved. Examples of fluorinated ethylene carbonate having 1 to 8 fluorines and derivatives thereof include monofluoroethylene carbonate, 4,4-difluoroethylene carbonate, 4,5-difluoroethylene carbonate, 4-fluoro-4-methylethylene carbonate, 4,5-difluoro-4-methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, 4,4-difluoro-5-methylethylene carbonate, 4-(fluoromethyl)-ethylene carbonate, 4-(difluoromethyl)-ethylene carbonate, 4-(trifluoromethyl)-ethylene carbonate, 4-(fluoromethyl)-4-fluoroethylene carbonate, 4-(fluoromethyl)-5-fluoroethylene carbonate, 4-fluoro-4,5-dimethylethylene carbonate, 4,5-difluoro-4,5-dimethylethylene carbonate, and 4,4-difluoro-5,5-dimethylethylene carbonate.

[0072] Among these, monofluoroethylene carbonate, 4,4-difluoroethylene carbonate, and 4,5-difluoroethylene carbonate are preferred because they impart high ionic conductivity to the electrolyte and facilitate the formation of a stable interface protective film. The fluorinated cyclic carbonate may be used alone or in any combination and ratio of two or more. The amount of the fluorinated cyclic carbonate (total amount when two or more types are used) is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, even more preferably 0.1% by mass or more, even more preferably 0.5% by mass or more, particularly preferably 1% by mass or more, most preferably 1.2% by mass or more, and preferably 10% by mass or less, more preferably 7% by mass or less, even more preferably 5% by mass or less, particularly preferably 3% by mass or less, and most preferably 2% by mass or less, in 100% by volume of the nonaqueous solvent. In addition, the content of the fluorinated cyclic carbonate when used as a nonaqueous solvent is preferably 1% by volume or more, more preferably 5% by volume or more, even more preferably 10% by volume or more, and preferably 50% by volume or less, more preferably 35% by volume or less, and even more preferably 25% by volume or less, in 100% by volume of the nonaqueous solvent. By using the content in the above range, it is possible to obtain a sufficient effect of improving high-temperature storage characteristics and cycle characteristics, and also to suppress the generation of unnecessary gas.

[0073] [1-4-3. Compounds containing isocyanato groups] The non-aqueous electrolyte solution may contain a compound having an isocyanato group (isocyanate group). Hereinafter, this may be referred to as an "isocyanate compound." The isocyanate compound is not particularly limited as long as it is an organic compound having at least one isocyanate group in the molecule, but the number of isocyanate groups in one molecule is preferably 1 or more and 4 or less, more preferably 1 or more and 3 or less, and even more preferably 1 or more and 2 or less.

[0074] The isocyanate compound is preferably a compound in which an isocyanate group is bonded to a compound having a linear or branched alkylene group, a cycloalkylene group, a structure in which a cycloalkylene group and an alkylene group are linked, an aromatic hydrocarbon group, a structure in which an aromatic hydrocarbon group and an alkylene group are linked, an ether structure (-O-), a structure in which an ether structure (-O-) and an alkylene group are linked, a carbonyl group (-C(=O)-), a structure in which a carbonyl group and an alkylene group are linked, a sulfonyl group (-S(=O)-), a structure in which a sulfonyl group and an alkylene group are linked, or a halogenated structure thereof, and more preferably a linear or branched alkylene group, a cycloalkylene group, a structure in which a cycloalkylene group and an alkylene group are linked, It is a compound in which an isocyanate group is bonded to a structure in which an aromatic hydrocarbon group or an aromatic hydrocarbon group and an alkylene group are linked, and more preferably, it is a compound in which an isocyanate group is bonded to a structure in which a cycloalkylene group and an alkylene group are linked. The molecular weight of the isocyanate compound is not particularly limited. The molecular weight is preferably 80 or more, more preferably 115 or more, more preferably 170 or more, and is 300 or less, more preferably 230 or less. Within this range, the solubility of the isocyanate compound in the non-aqueous electrolyte is easily ensured, and the effects of the present invention are easily manifested. The method for producing the isocyanate compound is not particularly limited, and it is possible to produce the isocyanate compound by arbitrarily selecting a known method. In addition, a commercially available product may be used.

[0075] The isocyanate compound is Examples of compounds having one isocyanate group include alkyl isocyanates such as methyl isocyanate, ethyl isocyanate, propyl isocyanate, isopropyl isocyanate, butyl isocyanate, and tertiary butyl isocyanate, cycloalkyl isocyanates such as cyclohexyl isocyanate, unsaturated isocyanates such as allyl isocyanate and propargyl isocyanate, and aromatic isocyanates such as phenyl isocyanate, trifluoromethylphenyl isocyanate, and p-toluenesulfonyl isocyanate;

[0076] Compounds having two isocyanato groups include monomethylene diisocyanate, dimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, octamethylene diisocyanate, decamethylene diisocyanate, 1,4-diisocyanato-2-butene, toluene diisocyanate, xylene diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-diisocyanate, Compounds such as anatocyclohexane, dicyclohexylmethane-4,4'-diisocyanate, bicyclo[2.2.1]heptane-2,5-diylbis(methylisocyanate), bicyclo[2.2.1]heptane-2,6-diylbis(methylisocyanate), isophorone diisocyanate, carbonyl diisocyanate, 1,4-diisocyanatobutane-1,4-dione, trimethylhexamethylene diisocyanate;

[0077] Compounds having three isocyanate groups include 1,6,11-triisocyanatoundecane, 4-isocyanatomethyl-1,8-octamethylene diisocyanate, 1,3,5-triisocyanatomethylbenzene, 1,3,5-tris(6-isocyanatohex-1-yl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and trimer compounds derived from compounds having at least two isocyanate groups in the molecule (e.g., biuret, isocyanurate, adduct, and bifunctional modified polyisocyanates, etc.); etc.

[0078] Of these, t-butyl isocyanate, cyclohexyl isocyanate, p-toluenesulfonyl isocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, decamethylene diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, dicyclohexylmethane-4,4'-diisocyanate, bicyclo[2.2.1]heptane-2,5-diylbis(methylisocyanate), bicyclo[2.2.1]heptane-2,6-diylbis(methylisocyanate), From the viewpoint of improving storage characteristics, compounds such as cyclohexyl isocyanate, p-toluenesulfonyl isocyanate, hexamethylene diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, dicyclohexylmethane-4,4'-diisocyanate, bicyclo[2.2.1]heptane-2,5-diylbis(methylisocyanate), bicyclo[2.2.1]heptane-2, 6-diylbis(methyl isocyanate), isophorone diisocyanate, and trimethylhexamethylene diisocyanate are more preferred, and cyclohexyl isocyanate, p-toluenesulfonyl isocyanate, hexamethylene diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, dicyclohexylmethane-4,4'-diisocyanate, bicyclo[2.2.1]heptane-2,5-diylbis(methyl isocyanate), and bicyclo[2.2.1]heptane-2,6-diylbis(methyl isocyanate) are even more preferred.

[0079] The isocyanate compound may be used alone or as a mixture of two or more kinds in any combination and ratio. The amount of the isocyanate compound (total amount when two or more kinds are used) is usually 0.001 mass% or more, preferably 0.1 mass% or more, more preferably 0.3 mass% or more, and usually 10 mass% or less, preferably 5 mass% or less, more preferably 3 mass% or less, in 100 mass% of the electrolytic solution. Within this range, it is easy to control the output characteristics, load characteristics, low-temperature characteristics, cycle characteristics, high-temperature storage characteristics, etc.

[0080] [1-4-4. Sulfur-containing organic compounds] The sulfur-containing organic compound is not particularly limited as long as it is an organic compound having at least one sulfur atom in the molecule, but is preferably an organic compound having an S=O group in the molecule, and examples thereof include chain sulfonate esters, cyclic sulfonate esters, chain sulfate esters, cyclic sulfate esters, chain sulfite esters, and cyclic sulfite esters. However, those corresponding to fluorosulfonates are not sulfur-containing organic compounds described later, but are included in fluorosulfonates, which are electrolytes described later.

[0081] Among these, chain sulfonate esters, cyclic sulfonate esters, chain sulfate esters, cyclic sulfate esters, chain sulfite esters and cyclic sulfite esters are preferred, and compounds having an S(=O)2 group are more preferred. More preferred are chain sulfonate esters and cyclic sulfonate esters, and more preferred are cyclic sulfonate esters. Specific examples of chain sulfonate esters, cyclic sulfonate esters, chain sulfate esters, cyclic sulfate esters, chain sulfite esters, and cyclic sulfite esters are shown below.

[0082] <Chain sulfonic acid ester> Fluorosulfonic acid esters such as methyl fluorosulfonate and ethyl fluorosulfonate. methanesulfonate esters such as methyl methanesulfonate, ethyl methanesulfonate, busulfan, methyl 2-(methanesulfonyloxy)propionate, ethyl 2-(methanesulfonyloxy)propionate, and ethyl methanesulfonyloxyacetate;

[0083] Alkenylsulfonate esters such as methyl vinylsulfonate, ethyl vinylsulfonate, allyl vinylsulfonate, propargyl vinylsulfonate, methyl allylsulfonate, ethyl allylsulfonate, allyl allylsulfonate, propargyl allylsulfonate, and 1,2-bis(vinylsulfonyloxy)ethane. Alkyl disulfonate esters such as methoxycarbonylmethyl methanedisulfonate, ethoxycarbonylmethyl methanedisulfonate, methoxycarbonylmethyl 1,2-ethanedisulfonate, ethoxycarbonylmethyl 1,2-ethanedisulfonate, methoxycarbonylmethyl 1,3-propanedisulfonate, ethoxycarbonylmethyl 1,3-propanedisulfonate, and 1-methoxycarbonylethyl 1,3-propanedisulfonate.

[0084] <Cyclic sulfonate ester> Sultone compounds such as 1,3-propane sultone, 1-fluoro-1,3-propane sultone, 2-fluoro-1,3-propane sultone, 3-fluoro-1,3-propane sultone, 1-methyl-1,3-propane sultone, 2-methyl-1,3-propane sultone, 3-methyl-1,3-propane sultone, 1-propene-1,3-sultone, 2-propene-1,3-sultone, 2-methyl-1-propene-1,3-sultone, 1,4-butane sultone, and 1,5-pentane sultone. Disulfonate compounds such as methylenemethane disulfonate and ethylenemethane disulfonate. Nitrogen-containing compounds such as 1,2,3-oxathiazolidine-2,2-dioxide. Phosphorus-containing compounds such as 1,2,3-oxathiaphoslan-2,2-dioxide.

[0085] <Chain sulfate ester> Dialkyl sulfate compounds such as dimethyl sulfate, ethyl methyl sulfate and diethyl sulfate.

[0086] <Cyclic sulfate ester> Alkylene sulfate compounds such as 1,2-ethylene sulfate, 1,2-propylene sulfate, 1,3-propylene sulfate, 1,2-butylene sulfate, 1,3-butylene sulfate, 1,4-butylene sulfate, 1,2-pentylene sulfate, 1,3-pentylene sulfate, 1,4-pentylene sulfate, and 1,5-pentylene sulfate.

[0087] <Chain sulfite ester> Dialkyl sulfite compounds such as dimethyl sulfite, ethyl methyl sulfite and diethyl sulfite.

[0088] <Cyclic sulfite> Alkylene sulfite compounds such as 1,2-ethylene sulfite, 1,2-propylene sulfite, 1,3-propylene sulfite, 1,2-butylene sulfite, 1,3-butylene sulfite, 1,4-butylene sulfite, 1,2-pentylene sulfite, 1,3-pentylene sulfite, 1,4-pentylene sulfite, and 1,5-pentylene sulfite.

[0089] Among these, methyl 2-(methanesulfonyloxy)propionate, ethyl 2-(methanesulfonyloxy)propionate, 2-propynyl 2-(methanesulfonyloxy)propionate, 1-methoxycarbonylethyl propanedisulfonate, 1-ethoxycarbonylethyl propanedisulfonate, 1-methoxycarbonylethyl butanedisulfonate, 1-ethoxycarbonylethyl butanedisulfonate, 1,3-propanesultone, 1-propene-1,3-sultone, 1,4-butanesultone, 1,2-ethylene sulfate, 1,2-ethylene From the viewpoint of improving the initial efficiency, sulfite, methyl methanesulfonate, and ethyl methanesulfonate are preferred, 1-methoxycarbonylethyl propanedisulfonate, 1-ethoxycarbonylethyl propanedisulfonate, 1-methoxycarbonylethyl butanedisulfonate, 1-ethoxycarbonylethyl butanedisulfonate, 1,3-propanesultone, 1-propene-1,3-sultone, 1,2-ethylene sulfate, and 1,2-ethylene sulfite are more preferred, and 1,3-propanesultone and 1-propene-1,3-sultone are even more preferred.

[0090] The sulfur-containing organic compound may be used alone or as a mixture of two or more kinds in any combination and ratio. The content of sulfur-containing organic compounds (total amount if two or more types) is 100 mass of non-aqueous electrolyte. %, it is usually 0.001% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, particularly preferably 0.3% by mass or more, particularly preferably 0.6% by mass or more, and usually 10% by mass or less, preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 2% by mass or less, particularly preferably 1.5% by mass or less, and most preferably 1.0% by mass or less. When it is within this range, it is easy to control the output characteristics, load characteristics, low-temperature characteristics, cycle characteristics, high-temperature storage characteristics, etc. of the battery.

[0091] [1-4-5. Phosphorus-containing organic compounds] The phosphorus-containing organic compound is not particularly limited as long as it is an organic compound having at least one phosphorus atom in the molecule. A battery using a non-aqueous electrolyte solution containing the phosphorus-containing organic compound can improve durability. The phosphorus-containing organic compound is preferably a phosphate ester, a phosphonate ester, a phosphinate ester, or a phosphite ester, more preferably a phosphate ester or a phosphonate ester, and even more preferably a phosphonate ester. These esters may have a substituent.

[0092] Specific examples of phosphorus-containing organic compounds include: Diethyl vinyl phosphate, allyl diethyl phosphate, propargyl diethyl phosphate, trivinyl phosphate, triallyl phosphate, tripropargyl phosphate, diallyl ethyl phosphate, dipropargyl ethyl phosphate, 2-acryloyloxyethyl diethyl phosphate, tris(2-acryloyloxyethyl)phosphate, trimethyl phosphonoformate, methyl diethyl phosphonoformate, methyl dipropyl phosphonoformate, methyl dibutyl phosphonoformate, triethyl phosphonoformate, ethyl dimethyl phosphonoformate, ethyl dipropyl phosphonoformate, ethyl dibutyl phosphonoformate, tripropyl phosphonoformate, propyl dimethyl phosphonoformate, propyl diethyl phosphonoformate, propyl dibutyl phosphonoformate, tributyl Phosphonoformate, butyl dimethylphosphonoformate, butyl diethylphosphonoformate, butyl dipropylphosphonoformate, methyl bis(2,2,2-trifluoroethyl)phosphonoformate, ethyl bis(2,2,2-trifluoroethyl)phosphonoformate, propyl bis(2,2,2-trifluoroethyl)phosphonoformate, butyl bis(2,2,2-trifluoroethyl)phosphonoformate, trimethyl phosphonoacetate, methyl diethylphosphonoacetate, methyl dipropylphosphonoacetate, methyl dibutylphosphonoacetate, triethyl phosphonoacetate, ethyl dimethylphosphonoacetate, ethyl dipropylphosphonoacetate, ethyl dibutylphosphonoacetate, tripropyl phosphonoacetate, propyl dimethylphosphonoacetate, propyl diethylphosphonoacetate, propyl dibutylphosphonoacetate, tributyl Phosphonoacetate, butyl dimethylphosphonoacetate, butyl diethylphosphonoacetate, butyl dipropylphosphonoacetate, methyl bis(2,2,2-trifluoroethyl)phosphonoacetate, ethyl bis(2,2,2-trifluoroethyl)phosphonoacetate, propyl bis(2,2,2-trifluoroethyl)phosphonoacetate, butyl bis(2,2,2-trifluoroethyl)phosphonoacetate, allyl dimethylphosphonoacetate, allyl diethylphosphonoacetate, 2-propynyl dimethylphosphonoacetate, 2-propynyl diethylphosphonoacetate, trimethyl 3-phosphonopropionate, methyl 3-(diethylphosphono)propionate, methyl 3-(dipropylphosphono)propionate, methyl 3-(dibutylphosphono)propionate, triethyl 3-phosphonopropionate, ethyl 3-(dimethylphosphono)propionate, ethyl 3-(dipropylphosphono)propionate, ethyl 3-(dibutylphosphono)propionate, tripropyl 3-phosphonopropionate, propyl 3 -(Dimethylphosphono)propionate, Propyl 3-(diethylphosphono)propionate, Propyl 3-(dibutylphosphono)propionate, Tributyl 3-phosphonopropionate, Butyl 3-(dimethylphosphono)propionate, Butyl 3-(diethylphosphono)propionate, Butyl 3-(dipropylphosphono)propionate, Methyl 3-(bis(2,2,2-trifluoroethyl)phosphono)propionate, Ethyl 3-(bis(2,2,2-trifluoroethyl)phosphono)propionate, Propyl 3-(bis(2,2,2-trifluoroethyl)phosphono)propionate, Butyl 3-(bis(2,2,2-trifluoroethyl)phosphono)propionate, Trimethyl 4-phosphonobutyrate, Methyl 4-(diethylphosphono)butyrate, Methyl Examples of the phosphonobutyrate include 4-(dipropylphosphono)butyrate, methyl 4-(dibutylphosphono)butyrate, triethyl 4-phosphonobutyrate, ethyl 4-(dimethylphosphono)butyrate, ethyl 4-(dipropylphosphono)butyrate, ethyl 4-(dibutylphosphono)butyrate, tripropyl 4-phosphonobutyrate, propyl 4-(dimethylphosphono)butyrate, propyl 4-(diethylphosphono)butyrate, propyl 4-(dibutylphosphono)butyrate, tributyl 4-phosphonobutyrate, butyl 4-(dimethylphosphono)butyrate, butyl 4-(diethylphosphono)butyrate, and butyl 4-(dipropylphosphono)butyrate.

[0093] The phosphorus-containing organic compound may be used alone or as a mixture of two or more kinds in any combination and ratio. The content of the phosphorus-containing organic compound (total amount when two or more kinds are used) is usually 0.001 mass% or more, preferably 0.01 mass% or more, more preferably 0.1 mass% or more, even more preferably 0.4 mass% or more, particularly preferably 0.6 mass% or more, and usually 10 mass% or less, preferably 5 mass% or less, more preferably 3 mass% or less, even more preferably 2 mass% or less, particularly preferably 1.2 mass% or less, and most preferably 0.9 mass% or less, in 100 mass% of the nonaqueous electrolyte. When the content is within this range, it is easy to control the output characteristics, load characteristics, low temperature characteristics, cycle characteristics, high temperature storage characteristics, etc.

[0094] [1-4-6. Organic compounds containing a cyano group] Examples of organic compounds having a cyano group include pentanenitrile, octanenitrile, decanenitrile, dodecanenitrile, crotononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, glutaronitrile, and 3,9-bis(2-cyanoethyl)-2,4,8,10-tetraoxaspiro[5,5]undecane, 1,2,3-tricyanopropane, 1,3,5-tricyanopentane, 1,4,7-tricyanoheptane, 1,2,4-tricyanobutane, 1,2,5-tricyanopentane, 1,2,6-tricyanohexane, 1,3,6-tricyanohexane, and 1,2,7-tricyanoheptane.

[0095] The organic compound having a cyano group is contained in a concentration of usually 0.001% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, particularly preferably 0.3% by mass or more, and usually 10% by mass or less, preferably 5% by mass or less, more preferably 3% by mass or less, particularly preferably 2% by mass or less, in 100% by mass of the non-aqueous electrolyte. When the concentration is within this range, it is easy to control the output characteristics, load characteristics, low-temperature characteristics, cycle characteristics, high-temperature storage characteristics, etc. The organic compound having a cyano group may be used alone or as a mixture of two or more kinds in any combination and ratio.

[0096] [1-4-7. Silicon-containing compounds] The silicon-containing compound is not particularly limited as long as it is a compound having at least one silicon atom in the molecule. , the durability characteristics can be improved. The silicon-containing compound is preferably a compound represented by formula (2-6).

[0097] [ka]

[0098] In formula (2-6), R 61 , R 62 and R 63 are independently a hydrogen atom, a halogen atom, or a hydrocarbon group having 1 to 10 carbon atoms, X 61 is an organic group containing at least one atom selected from the group consisting of oxygen atoms, nitrogen atoms, and silicon atoms. R 61 , R 62 and R 63 is preferably a hydrogen atom, a fluorine atom, a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, a sec-butyl group, an i-butyl group, a tert-butyl group or a phenyl group, and more preferably a methyl group.

[0099] X 61is an organic group containing at least one atom selected from the group consisting of oxygen, nitrogen and silicon atoms, preferably an organic group containing at least an oxygen atom or silicon atom. Here, the organic group refers to a group composed of one or more atoms selected from the group consisting of carbon, hydrogen, nitrogen, oxygen, silicon, sulfur, phosphorus and halogen atoms. Examples of the organic group include an alkyl group, an alkenyl group, an alkynyl group, an aryl group, an alkoxy group, a CN group, an isocyanato group, a fluoro group, an alkylsulfonic acid group and a trialkylsilyl group. Note that a part of the monovalent organic group may be substituted with a fluorine atom. The carbon number of the organic group is 1 or more, preferably 3 or more, more preferably 5 or more, and is usually 15 or less, preferably 12 or less, more preferably 8 or less.

[0100] Of these, alkylsulfonic acid groups, trialkylsilyl groups, boric acid groups, phosphoric acid groups and phosphorous acid groups are preferred. Silicon-containing compounds include: boric acid compounds such as tris(trimethylsilyl) borate, tris(trimethoxysilyl) borate, tris(triethylsilyl) borate, tris(triethoxysilyl) borate, tris(dimethylvinylsilyl) borate, and tris(diethylvinylsilyl) borate; phosphate compounds such as tris(trimethylsilyl) phosphate, tris(triethylsilyl) phosphate, tris(tripropylsilyl) phosphate, tris(triphenylsilyl) phosphate, tris(trimethoxysilyl) phosphate, tris(triethoxysilyl) phosphate, tris(triphenoxysilyl) phosphate, tris(dimethylvinylsilyl) phosphate, and tris(diethylvinylsilyl) phosphate; Phosphite compounds such as tris(trimethylsilyl) phosphite, tris(triethylsilyl) phosphite, tris(tripropylsilyl) phosphite, tris(triphenylsilyl) phosphite, tris(trimethoxysilyl) phosphite, tris(triethoxysilyl) phosphite, tris(triphenoxysilyl) phosphite, tris(dimethylvinylsilyl) phosphite, and tris(diethylvinylsilyl) phosphite; Sulfonic acid compounds such as trimethylsilyl methanesulfonate and trimethylsilyl tetrafluoromethanesulfonate; Disilane compounds such as hexamethyldisilane, hexaethyldisilane, 1,1,2,2-tetramethyldisilane, 1,1,2,2-tetraethyldisilane, 1,2-diphenyltetramethyldisilane, and 1,1,2,2-tetraphenyldisilane; etc.

[0101] Of these, tris(trimethylsilyl) borate, tris(trimethylsilyl) phosphate, tris(trimethylsilyl) phosphite, trimethylsilyl methanesulfonate, trimethylsilyl tetrafluoromethanesulfonate, hexamethyldisilane, hexaethyldisilane, 1,2-diphenyltetramethyldisilane, and 1,1,2,2-tetraphenyldisilane are preferred, and tris(trimethylsilyl) borate, tris(trimethylsilyl) phosphate, tris(trimethylsilyl) phosphite, and hexamethyldisilane are more preferred.

[0102] These silicon-containing compounds may be used alone or in any combination of two or more in any ratio. The silicon-containing compound (total amount when two or more kinds are used) is usually 0.001 mass% or more, preferably 0.1 mass% or more, more preferably 0.3 mass% or more, and usually 10 mass% or less, preferably 5 mass% or less, more preferably 3 mass% or less, in 100 mass% of the non-aqueous electrolyte. Within this range, it is easy to control the output characteristics, load characteristics, low-temperature characteristics, cycle characteristics, high-temperature storage characteristics, etc.

[0103] [1-4-8. Aromatic compounds] The aromatic compound is not particularly limited as long as it is an organic compound having at least one aromatic ring in the molecule. Examples of aromatic compounds include the following: Fluorobenzene, difluorobenzene, trifluorobenzene, tetrafluorobenzene, pentafluorobenzene, hexafluorobenzene, benzotrifluoride, cyclohexylbenzene, tert-butylbenzene, tert-amylbenzene, diphenyl carbonate, methyl phenyl carbonate, 2-phenylethyl acetate, 3-phenylpropyl acetate, methyl phenylacetate, ethyl phenylacetate, 2-phenylethyl phenylacetate, 3-phenylpropyl phenylacetate, methyl 3-phenylpropionate, ethyl 3-phenylpropionate, 2-phenylethyl 3-phenylpropionate, 3-phenylpropyl 3-phenylpropionate, methyl phenylsulfonate, 2-t ert-butylphenyl methylsulfonate, 4-tert-butylphenyl methylsulfonate, cyclohexylphenyl methylsulfonate, trimethylphenylsilane, tris(2-tert-butylphenyl)phosphate, tris(4-tert-butylphenyl)phosphate, tris(2-cyclohexylphenyl)phosphate, tris(4-cyclohexylphenyl)phosphate, diethylphenylphosphonate, diethylbenzylphosphonate, diethyl-(4-fluorobenzyl)phosphonate, 2-fluorophenylacetate, 4-fluorophenylacetate, 2,4-difluoroanisole, 2-fluorotoluene, 3-fluorotoluene, 4-fluorotoluene.

[0104] Among these, preferred are fluorobenzene, benzotrifluoride, cyclohexylbenzene, tert-butylbenzene, tert-amylbenzene, diphenyl carbonate, methylphenyl carbonate, 2-phenylethyl phenylacetate, 4-tert-butylphenyl methylsulfonate, cyclohexylphenyl methylsulfonate, tris(2-tert-butylphenyl)phosphate, tris(4-tert-butylphenyl)phosphate, tris(4-cyclohexylphenyl)phosphate, 2,4-difluoroanisole, and 2-fluorotoluene.

[0105] In addition to the above, 1-phenyl-1,3,3-trimethylindane, 2,3-dihydro-1,3-dimethyl-1-(2-methyl-2-phenylpropyl)-3-phenyl-1H-indane, 1-phenyl-1,3,3-trimethylindane, 2,3-dihydro-1,3-dimethyl-1-(2-methyl-2-phenylpropyl)-3-phenyl-1H-indane, 2,2-diphenylbutane, 3,3-diphenylpentane, 3,3-diphenylhexane, 4,4-diphenylheptane, 5,5-diphenyloctane, 6,6-diphenylnonane, 1,1-diphenyl-1,1-ditert-butyl-methane, 1,1-diphenylcyclohexane, 1,1-diphenylcyclopentane, 1,1-diphenyl-4-methylcyclohexane.

[0106] 1,3-bis(1-methyl-1-phenylethyl)-benzene, 1,4-bis(1-methyl-1-phenylethyl)-benzene, 1-phenyl-1,3,3-trimethylindane, 2,2-diphenylbutane, 3,3-diphenylpentane, 1,1-diphenyl-1,1-ditert-butyl-methane, 1,1-diphenylcyclohexane, 1,1-diphenylcyclopentane, 1,1-diphenyl-4-methylcyclohexane, 1,3-bis(1-methyl-1-phenylethyl)-benzene, 1,4-bis(1-methyl-1-phenylethyl)-benzene, 1-phenyl-1,3,3-trimethylindane, 2,2-diphenylbutane, 1,1-diphenylcyclohexane, 1,1-diphenyl-4-methylcyclohexane, 1,3- Examples include bis(1-methyl-1-phenylethyl)-benzene, 1,4-bis(1-methyl-1-phenylethyl)-benzene, 1-phenyl-1,3,3-trimethylindane, 1,1-diphenylcyclohexane, 1,1-diphenyl-4-methylcyclohexane, 1,3-bis(1-methyl-1-phenylethyl)-benzene, 1,4-bis(1-methyl-1-phenylethyl)-benzene, 1-phenyl-1,3,3-trimethylindane, 1,1-diphenylcyclohexane, 1,3-bis(1-methyl-1-phenylethyl)-benzene, 1,4-bis(1-methyl-1-phenylethyl)-benzene, 1-phenyl-1,3,3-trimethylindane, and 1-phenyl-1,3,3-trimethylindane.

[0107] The aromatic compound may be used alone or in combination of two or more. In the total amount (100% by mass) of the non-aqueous electrolyte, the amount of the aromatic compound (total amount when two or more types are used) is usually 0.001% by mass or more, preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, even more preferably 0.4% by mass or more, and usually 10% by mass or less, preferably 8% by mass or less, more preferably 5% by mass or less, even more preferably 3% by mass or less, and particularly preferably 2.5% by mass or less. Within the above range, This makes it easier for the effects of the present invention to be realized, and also makes it possible to prevent an increase in the resistance of the battery.

[0108] [1-4-9. Fluorine-free carboxylic acid esters] The fluorine-free carboxylate can be used as a solvent as described above. The fluorine-free carboxylate is not particularly limited as long as it is a carboxylate that does not have a fluorine atom in the molecule. Examples of the non-fluorine-containing chain carboxylate ester include the following.

[0109] Methyl acetate, ethyl acetate, n-propyl acetate, n-butyl acetate, methyl propionate, ethyl propionate, n-propyl propionate, n-butyl propionate, methyl butyrate, ethyl butyrate, n-propyl butyrate, n-butyl butyrate, methyl valerate, ethyl valerate, n-propyl valerate, n-butyl valerate, methyl pivalate, ethyl pivalate, n-propyl pivalate, n-butyl pivalate.

[0110] Among these, from the viewpoint of improving ionic conductivity by reducing the viscosity of the electrolyte, methyl acetate, ethyl acetate, n-propyl acetate, n-butyl acetate, methyl propionate, ethyl propionate, n-propyl propionate and n-butyl propionate are more preferable, and propionate Methyl, ethyl propionate, n-propyl propionate and n-butyl propionate are more preferred, with ethyl propionate and n-propyl propionate being particularly preferred.

[0111] The non-fluorine-containing carboxylic acid ester may be used alone or in any combination of two or more kinds in any ratio. The amount of the fluorine-free carboxylate ester (total amount when two or more kinds are used) is usually 0.001% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, even more preferably 0.3% by mass or more, particularly preferably 0.6% by mass or more, and usually 10% by mass or less, preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 2% by mass or less, and particularly preferably 1% by mass or less. In addition, the content of the fluorine-free carboxylate ester when used as a non-aqueous solvent is preferably 1% by volume or more, more preferably 5% by volume or more, even more preferably 10% by volume or more, even more preferably 20% by volume or more, and usually 50% by volume or less, more preferably 45% by volume or less, and even more preferably 40% by volume or less, in 100% by volume of the non-aqueous solvent. If it is within such a range, the increase in the negative electrode resistance is suppressed, and it is easy to control the output characteristics, load characteristics, low-temperature characteristics, cycle characteristics, and high-temperature storage characteristics.

[0112] [1-4-10. Cyclic compounds with multiple ether bonds] The cyclic compound having a plurality of ether bonds is not particularly limited as long as it is a cyclic compound having a plurality of ether bonds in the molecule. The cyclic compound having a plurality of ether bonds contributes to improving the high-temperature storage characteristics of the battery, and can improve the durability characteristics of the non-aqueous electrolyte battery.

[0113] Examples of cyclic compounds having a plurality of ether bonds include tetrahydrofuran, methyltetrahydrofuran, tetrahydropyran, and methyltetrahydropyran. The cyclic compound having a plurality of ether bonds may be used alone, or may be used in any combination and ratio of two or more. The content of the cyclic compound having a plurality of ether bonds (total amount when two or more) is usually 0.001% by mass or more in 100% by mass of the non-aqueous electrolyte, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, particularly preferably 0.3% by mass or more, and usually 10% by mass or less, preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 2% by mass or less. When the above range is satisfied, it is easy to control the output characteristics, load characteristics, low-temperature characteristics, cycle characteristics, high-temperature storage characteristics, etc.

[0114] [1-4-11. Compounds with an isocyanuric acid skeleton] Examples of compounds having an isocyanuric acid skeleton include the following. Trivinyl isocyanurate, tri(1-propenyl)isocyanurate, triallyl isocyanurate, trimethallyl isocyanurate, methyl diallyl isocyanurate, ethyl diallyl isocyanurate, diethyl allyl isocyanurate, diethyl vinyl isocyanurate, tri(propargyl)isocyanurate, tris(2-acryloxymethyl)isocyanurate, tris(2-acryloxyethyl)isocyanurate, tris(2-methacryloxymethyl)isocyanurate, tris(2-methacryloxyethyl)isocyanurate Examples of the isocyanurate include isocyanurate and ε-caprolactone-modified tris-(2-acryloxyethyl)isocyanurate. Among these, triallyl isocyanurate, trimethallyl isocyanurate, tris(2-acryloxyethyl)isocyanurate, tris(2-methacryloxyethyl)isocyanurate and ε-caprolactone-modified tris-(2-acryloxyethyl)isocyanurate are preferred, and triallyl isocyanurate and tris(2-acryloxyethyl)isocyanurate are particularly preferred because of their large effect of improving continuous charging characteristics. These may be used alone or in combination of two or more kinds.

[0115] The content of the compound having an isocyanuric acid skeleton (total amount when two or more kinds are used) is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and most preferably 0.2% by mass or more in 100% by mass of the non-aqueous electrolyte. It is also preferable to use it at a content of 5% by mass or less, more preferably 3% by mass or less, and most preferably 2% by mass or less. By using it at the above content, it is possible to obtain a sufficient effect of improving high-temperature storage characteristics and continuous charging characteristics, and to suppress unnecessary resistance increase.

[0116] [1-4-12. Electrolyte additives] Among the additives, examples of additives that act as electrolytes include the following (monofluorophosphates, difluorophosphates, borates, oxalates, and fluorosulfonates). These salts are particularly preferably lithium salts. The total content of borate, oxalate, and fluorosulfonate in the non-aqueous electrolyte is preferably 0.01% by mass or more, and more preferably 0.1% by mass or more, and is preferably 20% by mass or less, and more preferably 10% by mass or less.

[0117] [1-4-12-1. Monofluorophosphates, difluorophosphates] The monofluorophosphate and the difluorophosphate are not particularly limited as long as they are salts having at least one monofluorophosphoric acid or difluorophosphoric acid structure in the molecule. By using an electrolyte containing at least one selected from the monofluorophosphate and the difluorophosphate, the durability of the nonaqueous electrolyte battery can be improved. In addition, by applying the electrolyte to a nonaqueous secondary battery having a specific positive electrode described later, a nonaqueous electrolyte battery having a high capacity retention rate after high-temperature storage, a small amount of stored gas after high-temperature storage, and a small amount of metal elution from the positive electrode and high safety can be obtained.

[0118] The counter cation in the monofluorophosphate and difluorophosphate is not particularly limited, and may be lithium, sodium, potassium, magnesium, calcium, NR 121 R 122 R 123 R 124 (In the formula, R 121 ~R 124 are independently a hydrogen atom or an organic group having 1 to 12 carbon atoms. 121 ~R 124 The organic group having 1 to 12 carbon atoms represented by the formula (I) is not particularly limited, and examples thereof include an alkyl group which may be substituted with a fluorine atom, a cycloalkyl group which may be substituted with a halogen atom or an alkyl group, an aryl group which may be substituted with a halogen atom or an alkyl group, and a nitrogen atom-containing heterocyclic group which may have a substituent. 121 ~R 124 are each preferably a hydrogen atom, an alkyl group, a cycloalkyl group, a nitrogen atom-containing heterocyclic group, etc. As the counter cation, lithium, sodium or potassium is preferred, and among these, lithium is preferred.

[0119] Examples of monofluorophosphates and difluorophosphates include lithium monofluorophosphate, sodium monofluorophosphate, potassium monofluorophosphate, lithium difluorophosphate, sodium difluorophosphate, potassium difluorophosphate, and the like, with lithium monofluorophosphate and lithium difluorophosphate being preferred, and lithium difluorophosphate being more preferred.

[0120] The total content of monofluorophosphate and difluorophosphate in the non-aqueous electrolyte is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, particularly preferably 0.3% by mass or more, and most preferably 0.5% by mass or more. It is also preferably 8% by mass or less, more preferably 4% by mass or less, particularly preferably 2% by mass or less, and most preferably 1.5% by mass or less. If the total content of monofluorophosphate and difluorophosphate is within this range, When used as a non-aqueous electrolyte battery, it has a large capacity after high-temperature storage and suppresses battery swelling and metal elution, resulting in excellent high-temperature life and safety, and avoiding increases in the manufacturing costs of non-aqueous electrolyte batteries. The monofluorophosphates and difluorophosphates may be used alone or as a mixture of two or more kinds in any combination and in any ratio. In the present invention, the monofluorophosphates and difluorophosphates include those produced in a nonaqueous electrolyte solution and a nonaqueous electrolyte battery.

[0121] [1-4-12-2. Borates] The borate is not particularly limited as long as it is a salt having at least one boron atom in the molecule. However, the oxalate is not a borate, but is included in the oxalate described below. In the battery of the present invention, the durability can be improved.

[0122] Examples of the counter cation in the borate include lithium, sodium, potassium, magnesium, calcium, rubidium, cesium, and barium, with lithium being preferred. The borate is preferably a lithium salt, and a lithium borate salt can also be suitably used. Examples include LiBF4, LiBF3CF3, LiBF3C2F5, LiBF3C3F7, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, and LiBF2(C2F5SO2)2. Among them, LiBF4 is more preferred because it has the effect of improving the initial charge-discharge efficiency and high-temperature cycle characteristics.

[0123] The borate may be used alone or as a mixture of two or more kinds in any combination and in any ratio. The amount of borate (total amount when two or more kinds are used) is usually 0.05% by mass or more, preferably 0.1% by mass or more, more preferably 0.2% by mass or more, even more preferably 0.3% by mass or more, particularly preferably 0.4% by mass or more, and is usually 10.0% by mass or less, preferably 5.0% by mass or less, more preferably 3.0% by mass or less, even more preferably 2.0% by mass or less, particularly preferably 1.0% by mass or less. Within this range, side reactions in the battery negative electrode are suppressed and the resistance is less likely to increase.

[0124] [1-4-12-3. Oxalate] The oxalate is not particularly limited as long as it is a compound having at least one oxalic acid structure in the molecule, and can improve the durability of the battery of the present invention. The oxalate is preferably a metal salt represented by the following formula (9): This salt has an oxalato complex as the anion.

[0125] [ka]

[0126] In formula (9), M 2 is an element selected from the group consisting of Groups 1 and 2 and aluminum (Al) in the periodic table, and M 3 is an element selected from the group consisting of transition metals, groups 13, 14, and 15 of the periodic table, and R 91is a group selected from the group consisting of halogen, an alkyl group having from 1 to 11 carbon atoms, and a halogen-substituted alkyl group having from 1 to 11 carbon atoms, a and b are positive integers, c is 0 or a positive integer, and d is an integer from 1 to 3.

[0127] M 2 In terms of the battery characteristics when used in the non-aqueous electrolyte battery of the present invention, Of these, lithium, potassium, magnesium or calcium is preferred, with lithium being particularly preferred. M 3 In terms of electrochemical stability when used in a non-aqueous electrolyte battery, boron and phosphorus are particularly preferred. R 91 Examples of the alkyl group include fluorine, chlorine, a methyl group, a trifluoromethyl group, an ethyl group, a pentafluoroethyl group, a propyl group, an isopropyl group, a butyl group, a sec-butyl group, a tert-butyl group, and the like, and fluorine or a trifluoromethyl group is preferred.

[0128] Examples of the metal salt represented by formula (9) include the following. Lithium oxalatoborate salts such as lithium difluorooxalatoborate and lithium bis(oxalato)borate; Lithium oxalatophosphate salts such as lithium tetrafluorooxalatophosphate, lithium difluorobis(oxalato)phosphate, and lithium tris(oxalato)phosphate; Of these, lithium bis(oxalato)borate and lithium difluorobis(oxalato)phosphate are preferred, with lithium bis(oxalato)borate being more preferred.

[0129] The oxalate may be used alone or as a mixture of two or more kinds in any combination and in any ratio. The amount of oxalate (the total amount when two or more types are used) is usually 0.001% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, particularly preferably 0.3% by mass or more, and is usually 10% by mass or less, preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 2% by mass or less, particularly preferably 1% by mass or less. Within this range, it is easy to control the output characteristics, load characteristics, low-temperature characteristics, cycle characteristics, high-temperature storage characteristics, and the like.

[0130] [1-4-12-4. Fluorosulfonates] The fluorosulfonate is not particularly limited as long as it is a salt having at least one fluorosulfonic acid structure in the molecule, and can improve the durability of the battery of the present invention. The counter cation in the fluorosulfonate is not particularly limited, and may be lithium, sodium, potassium, rubidium, cesium, magnesium, calcium, barium, or NR 131 R 132 R 133 R 134 (In the formula, R 131 ~R 134 are each independently a hydrogen atom or an organic group having 1 to 12 carbon atoms. As the counter cation, lithium, sodium or potassium is preferred, and among these, lithium is preferred.

[0131] Examples of fluorosulfonates include lithium fluorosulfonate, sodium fluorosulfonate, potassium fluorosulfonate, rubidium fluorosulfonate, and cesium fluorosulfonate, and lithium fluorosulfonate is preferred. Imide salts having a fluorosulfonic acid structure, such as lithium bis(fluorosulfonyl)imide, can also be used as fluorosulfonates.

[0132] The fluorosulfonate may be used alone or as a mixture of two or more kinds in any combination and in any ratio. The content of the fluorosulfonate salt (the total amount when two or more kinds are used) is usually 0.05% by mass or more, preferably 0.1% by mass or more, more preferably 0.2% by mass or more, even more preferably 0.3% by mass or more, and particularly preferably 0.4% by mass or more, and is usually 10% by mass or less, preferably 8% by mass or less, more preferably 5% by mass or less, even more preferably 2% by mass or less, and particularly preferably 1% by mass or less. Within this range, side reactions in the battery are prevented. It has little stress and is less likely to increase resistance.

[0133] [2.Nonaqueous electrolyte battery] The nonaqueous electrolyte battery of the present invention is a nonaqueous electrolyte battery that includes a positive electrode having a positive electrode active material capable of absorbing and releasing metal ions, and a negative electrode having a negative electrode active material capable of absorbing and releasing metal ions, and contains a nonaqueous electrolyte.

[0134] [2-1. Non-aqueous electrolyte] As the non-aqueous electrolyte solution, the above-mentioned non-aqueous electrolyte solution is used. Note that, within the scope of the present invention, it is also possible to mix the above-mentioned non-aqueous electrolyte solution with other non-aqueous electrolyte solutions.

[0135] [2-2. Negative electrode] The negative electrode active material used in the negative electrode will be described below. There are no particular limitations on the negative electrode active material as long as it is capable of electrochemically absorbing and releasing metal ions such as lithium ions. Specific examples include carbonaceous materials, alloy materials, lithium-containing metal composite oxide materials, and the like. These may be used alone or in any combination of two or more.

[0136] <Negative electrode active material> Examples of the negative electrode active material include carbonaceous materials, alloy materials, and lithium-containing metal composite oxide materials. Examples of carbonaceous materials include (1) natural graphite, (2) artificial graphite, (3) amorphous carbon, (4) carbon-coated graphite, (5) graphite-coated graphite, and (6) resin-coated graphite.

[0137] (1) Examples of natural graphite include scaly graphite, scaly graphite, soil graphite, and / or graphite particles obtained by treating these graphites as raw materials with treatments such as spheroidization and densification. Among these, from the viewpoints of particle packing and charge / discharge rate characteristics, spherical or ellipsoidal graphite that has been subjected to a spheroidization treatment is particularly preferred.

[0138] (2) Examples of artificial graphite include those produced by graphitizing organic compounds such as coal tar pitch, coal-based heavy oil, atmospheric residual oil, petroleum-based heavy oil, aromatic hydrocarbons, nitrogen-containing cyclic compounds, sulfur-containing cyclic compounds, polyphenylene, polyvinyl chloride, polyvinyl alcohol, polyacrylonitrile, polyvinyl butyral, natural polymers, polyphenylene silicide, polyphenylene oxide, furfuryl alcohol resin, phenol-formaldehyde resin, and imide resin at a temperature usually in the range of 2500°C or higher and usually 3200°C or lower, and pulverizing and / or classifying as necessary. In this case, silicon-containing compounds and boron-containing compounds can also be used as graphitization catalysts. In addition, examples of artificial graphite include those obtained by graphitizing mesocarbon microbeads separated during the heat treatment process of pitch. In addition, examples of artificial graphite include granulated particles consisting of primary particles. Examples of such graphite particles include mesocarbon microbeads and graphite particles in which a plurality of flat particles are aggregated or bonded together so that the oriented planes are non-parallel, and which are obtained by mixing a graphitizable carbonaceous material powder such as coke with a graphitizable binder such as tar or pitch and a graphitization catalyst, graphitizing the mixture, and pulverizing the mixture as necessary.

[0139] (3) Examples of amorphous carbon include amorphous carbon particles obtained by using graphitizable carbon precursors such as tar and pitch as raw materials and heat-treating them at least once in a temperature range in which graphitization does not occur (400 to 2200°C), and amorphous carbon particles obtained by using non-graphitizable carbon precursors such as resin as raw materials and heat-treating them.

[0140] (4) Carbon-coated graphite includes natural graphite and / or artificial graphite, and tar, pitch, and resin. Examples of the carbon-graphite composite include a carbon precursor, which is an organic compound such as benzene, toluene, methane, propane, and the like, and a heat treatment is performed at least once in the range of 400 to 2300°C to obtain a core graphite, which is a natural graphite and / or artificial graphite, and the core graphite is coated with amorphous carbon. The composite may be in the form of a coating on the entire or part of the surface, or a composite of a plurality of primary particles using carbon originating from the carbon precursor as a binder. A carbon-graphite composite can also be obtained by reacting natural graphite and / or artificial graphite with a hydrocarbon gas such as benzene, toluene, methane, propane, or aromatic volatile matter at a high temperature to deposit carbon on the graphite surface (CVD).

[0141] (5) Examples of graphite-coated graphite include graphite-coated graphite in which natural graphite and / or artificial graphite is mixed with a carbon precursor which is an easily graphitizable organic compound such as tar, pitch, or resin, and the mixture is heat-treated at least once in the range of about 2400 to 3200°C to obtain natural graphite and / or artificial graphite as core graphite, and the graphitized material coats the entire or part of the surface of the core graphite.

[0142] (6) Examples of resin-coated graphite include resin-coated graphite in which natural graphite and / or artificial graphite is mixed with a resin, etc., and dried at a temperature of less than 400°C to obtain natural graphite and / or artificial graphite as core graphite, and the core graphite is coated with a resin, etc. The carbonaceous materials (1) to (6) may be used alone or as a mixture of two or more kinds in any combination and ratio. The alloy-based material used as the negative electrode active material is not particularly limited, and may be any of lithium alone, elemental metals and alloys that form lithium alloys, or compounds such as oxides, carbides, nitrides, silicides, sulfides, or phosphides thereof, so long as it is capable of absorbing and releasing lithium. As elemental metals and alloys that form lithium alloys, materials containing metal / metalloid elements (i.e., excluding carbon) of Groups 13 and 14 are preferred, and elemental metals of aluminum, silicon, and tin and alloys or compounds containing these atoms are more preferred. These may be used alone or in any combination and ratio of two or more.

[0143] <Physical properties of carbonaceous materials> When a carbonaceous material is used as the negative electrode active material, it is desirable for the material to have the following physical properties.

[0144] (X-ray parameters) The d value (interlayer distance) of the lattice plane (002 plane) of the carbonaceous material determined by X-ray diffraction according to the Gakushin method is usually 0.335 nm or more and usually 0.360 nm or less, preferably 0.350 nm or less, and more preferably 0.345 nm or less. The crystallite size (Lc) of the carbonaceous material determined by X-ray diffraction according to the Gakushin method is preferably 1.0 nm or more, and more preferably 1.5 nm or more.

[0145] (Volume-based average particle size) The volume-based average particle size of the carbonaceous material is the volume-based average particle size (median diameter) determined by a laser diffraction / scattering method, and is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and particularly preferably 7 μm or more, and is usually 100 μm or less, preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 25 μm or less. If the volume-based average particle size is below the above range, the irreversible capacity increases, which may lead to a loss of initial battery capacity, whereas if it exceeds the above range, the coating surface is likely to be non-uniform when the electrode is prepared by coating, which may be undesirable in the battery manufacturing process.

[0146] (BET specific surface area) The BET specific surface area of ​​a carbonaceous material is the value of the specific surface area measured using the BET method. 0.1m 2 ·g -1 Above 0.7m 2 ·g -1 More than 1.0m is preferable. 2 ·g -1 More preferably, 1.5m or more 2 ·g -1 More than 100m is particularly preferable. 2 ·g -1 Less than or equal to 25m 2·g -1 Less than 15m is preferable 2 ·g -1 Less than 10m is more preferable. 2 ·g -1 The following are particularly preferred:

[0147] If the BET specific surface area is below this range, the lithium acceptance during charging when used as a negative electrode material is likely to be poor, lithium is likely to precipitate on the electrode surface, and stability may decrease. On the other hand, if the BET specific surface area exceeds this range, the reactivity with a non-aqueous electrolyte increases when used as a negative electrode material, gas generation is likely to increase, and it may be difficult to obtain a preferable battery.

[0148] <Negative electrode structure and manufacturing method> The electrode can be manufactured by any known method as long as it does not significantly impair the effects of the present invention. For example, the electrode can be formed by adding a binder, a solvent, and, if necessary, a thickener, a conductive material, a filler, etc. to the negative electrode active material to form a slurry, applying the slurry to a current collector, drying the slurry, and pressing the current collector. When an alloy-based material is used, a method of forming a thin film layer (negative electrode active material layer) containing the above-mentioned negative electrode active material by a method such as vapor deposition, sputtering, or plating may also be used.

[0149] (electrode density) There are no particular restrictions on the structure of the electrode when the negative electrode active material is made into an electrode, but the density of the negative electrode active material present on the current collector must be less than 1 g cm -3 More than 1.2 g cm is preferable. -3 More preferably, 1.3 g cm -3 More than 2.2 g cm is particularly preferable. -3 Less than 2.1 g cm is preferable. -3 Less than 2.0 g cm is preferable. -3 Less than 1.9 g cm is more preferable. -3 The following are particularly preferred:

[0150] If the density of the negative electrode active material present on the current collector exceeds the above range, the negative electrode active material particles may be destroyed, leading to an increase in the initial irreversible capacity and a deterioration in the high current density charge / discharge characteristics due to a decrease in the permeability of the non-aqueous electrolyte solution near the current collector / negative electrode active material interface. If the density is below the above range, the conductivity between the negative electrode active materials may decrease, the battery resistance may increase, and the capacity per unit volume may decrease.

[0151] [2-3. Positive electrode] <Cathode active material> The positive electrode active material (lithium transition metal compound) used in the positive electrode will be described below.

[0152] <Lithium transition metal compounds> A lithium transition metal compound is a compound having a structure capable of desorbing and inserting Li ions, and the lithium transition metal compound used in the present invention is represented by the formula showing the space group below. In addition, it is preferable that the compound has a layered structure that allows two-dimensional diffusion of lithium ions. Here, the layered structure will be described in more detail. Representative crystal systems of those having a layered structure include those belonging to the α-NaFeO2 type such as LiCoO2 and LiNiO2, which are hexagonal crystal systems and, due to their symmetry, are classified into the space group

[0153]

number

[0154] (hereinafter referred to as "layered R(-3)m structure"). However, layered LiMeO2 is not limited to the layered R(-3)m structure. In addition, LiMnO2, also known as layered Mn, is a layered compound in the orthorhombic system with the space group Pm2m, and Li2MnO3, also known as the 213 phase, is a Li[Li 1 / 3 Mn 2 / 3 ]O2, and has a monoclinic space group C2 / m structure, but it also has a Li layer and [Li 1 / 3 Mn 2 / 3 ] layer and an oxygen layer are stacked.

[0155] (Lithium transition metal compounds) The lithium transition metal compound according to the present invention is a lithium transition metal compound represented by the following composition formula (I). Li 1+x M 4 O2···(I) In formula (I), x is -0.1 or more and 0.5 or less. In particular, the lower limit of x is preferably -0.04 or more, more preferably -0.03 or more, particularly preferably -0.02 or more, and most preferably -0.01 or more. The upper limit of x is more preferably 0.2 or less, particularly preferably 0.1 or less, and most preferably 0.05 or less. If x is within the above range, it is preferable because sufficient charge / discharge capacity is obtained.

[0156] Furthermore, in formula (I), M 4 is a plurality of elements including at least Ni and Co, and Ni / M 4 The molar ratio is 0.45 or more and 1.0 or less. More preferably, M 4 contains at least Ni, Mn and Co, and the Ni / (Ni+Mn+Co) molar ratio is preferably 0.45 or more. The lower limit of the Ni / (Ni+Mn+Co) molar ratio is more preferably 0.55 or more, even more preferably 0.65 or more, particularly preferably 0.75 or more, and most preferably 0.85 or more. The upper limit of the Ni / (Ni+Mn+Co) molar ratio is usually 0.98 or less, more preferably 0.95 or less, even more preferably 0.93 or less, and most preferably 0.90 or less.

[0157] If the Ni / (Ni+Mn+Co) molar ratio is within the above range, the ratio of Ni involved in charging and discharging becomes sufficiently large, and the battery has a high capacity, which is preferable. Furthermore, the Mn / (Ni+Mn+Co) molar ratio is not particularly limited, but is usually 0 or more and 0.32 or less. The lower limit of the Mn / (Ni+Mn+Co) molar ratio is preferably 0.05 or more, more preferably 0.08 or more, even more preferably 0.10 or more, particularly preferably 0.12 or more, and most preferably 0.14 or more. The upper limit of the Mn / (Ni+Mn+Co) molar ratio is preferably 0.28 or less, more preferably 0.26 or less, even more preferably 0.25 or less, particularly preferably 0.24 or less, and most preferably 0.23 or less.

[0158] It is preferable that the Mn / (Ni+Mn+Co) molar ratio is within the above range, since the ratio of Mn that is not involved in charging and discharging becomes sufficiently small, resulting in a high-capacity battery. The lower limit of the Co / (Ni+Mn+Co) molar ratio is preferably 0.05 or more, more preferably 0.08 or more, particularly preferably 0.10 or more, and most preferably 0.15 or more. The upper limit of the Co / (Ni+Mn+Co) molar ratio is not particularly limited, but is preferably 0.33 or less, more preferably 0.30 or less, even more preferably 0.28 or less, particularly preferably 0.26 or less, and most preferably 0.24 or less.

[0159] If the molar ratio of Co / (Ni+Mn+Co) is within the above range, the charge / discharge capacity becomes large, which is preferable. In the above composition formula (I), the atomic ratio of the oxygen amount is described as 2 for convenience, but some degree of non-stoichiometry is acceptable. Also, x in the above formula (I) is the composition of the lithium transition metal compound at the manufacturing stage. Usually, after the battery is assembled, the batteries available on the market are Aging is performed. Therefore, the amount of Li in the positive electrode may be lost due to charging and discharging.

[0160] In addition, a foreign element may be introduced into the lithium transition metal compound. The foreign element is selected from one or more of B, Na, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Ru, Rh, Pd, Ag, In, Sb, Te, Ba, Ta, Mo, W, Re, Os, Ir, Pt, Au, Pb, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Bi, N, F, S, Cl, Br, I, As, Ge, P, Pb, Sb, Si, and Sn. Among them, at least one element selected from the group consisting of Fe, Cu, W, Mo, Nb, V, Ta, Mg, Al, Ti, Zr, Zn, Ca, Be, B, Bi, Li, Na, and K is preferable.

[0161] These foreign elements may be incorporated into the crystal structure of the lithium transition metal compound, or may not be incorporated into the crystal structure of the lithium transition metal compound and may be unevenly distributed as a single element or a compound on the particle surface or grain boundaries. (Properties of positive electrode active materials containing lithium transition metal compounds or lithium transition metal compounds)

[0162] (1) Sulfates The positive electrode active material may contain a sulfate. The content of the sulfate that can be contained in the positive electrode active material is not particularly limited, but is preferably 15 μmol / g or more because the gas generation suppression effect and the effect of increasing the capacity retention rate after storage due to the silyl ester compound are easily and sufficiently exhibited. Also, it is more preferably 20 μmol / g or more, even more preferably 25 μmol / g or more, particularly preferably 32 μmol / g or more, and most preferably 35 μmol / g or more.The upper limit is preferably 100 μmol / g or less, more preferably 80 μmol / g or less, even more preferably 60 μmol / g or less, particularly preferably 50 μmol / g or less, and most preferably 30 μmol / g or less, because gas generation due to side reactions becomes large. The sulfate contained in the positive electrode active material can be measured, for example, by water extraction ion chromatography.

[0163] (2)Ni average valence The lithium transition metal compound contained in the positive electrode active material has an average Ni valence in an uncharged state that is not particularly limited, but is preferably 2.1 or more because it can increase the Ni ratio and make the battery have a high capacity. It is more preferably 2.3 or more, even more preferably 2.5 or more, particularly preferably 2.55 or more, and most preferably 2.6 or more. The upper limit is preferably 3 or less, more preferably 2.9 or less, particularly preferably 2.8 or less, and most preferably 2.7 or less, because the structural stability of the active material decreases.

[0164] Here, the Ni valence in the present invention will be described in detail. First, when the composition formula of the lithium transition metal compound is rewritten as the following composition formula (I'), M' is an element composed of Li, Ni and Co, or Li, Ni, Mn and Co. LiM'O2···(I') In the above composition formula (I'), the atomic ratio of oxygen is described as 2 for convenience, but some degree of non-stoichiometry is acceptable. When there is non-stoichiometry, the atomic ratio of oxygen is usually in the range of 2±0.2, preferably in the range of 2±0.15, more preferably in the range of 2±0.12, and even more preferably in the range of 2±0.16. Preferably, the range is 2±0.10, and more preferably, the range is 2±0.05.

[0165] Furthermore, the lithium transition metal compound is particularly preferably one in which the atomic structure in the M' site in the composition formula (I') is represented by the following formula (II). M'=Li z / (2+z) {(Ni (1+y) / 2 Mn (1-y) / 2 ) 1-x Co x} 2 / (2+z) (II) Here, the chemical meaning of the Li composition (z and x) in the lithium nickel manganese cobalt composite oxide, which is a suitable composition for the lithium transition metal compound, will be explained in more detail below.

[0166] As mentioned above, the layered structure is not necessarily limited to the R(-3)m structure, but it is preferable from the standpoint of electrochemical performance that it can be attributed to the R(-3)m structure. To determine x, y, and z in the composition formula of the lithium transition metal compound, each transition metal and Li are analyzed by an inductively coupled plasma atomic emission spectrometry (ICP-AES), and then the Li surface impurity is analyzed by water extraction ion chromatography to determine the Li / Ni / Mn / Co ratio of the lithium transition metal compound.

[0167] From a structural point of view, it is considered that the Li associated with z is substituted into the same transition metal site. Here, due to the Li associated with z, the average valence of Ni becomes greater than divalent (trivalent Ni is generated) due to the principle of charge neutrality. Since z increases the average valence of Ni, it is an index of the Ni valence (proportion of Ni(III)). In addition, when calculating the Ni valence (m) associated with the change in z and z' from the above composition formula, assuming that the Co valence is trivalent and the Mn valence is tetravalent,

[0168]

number

[0169] This calculation result means that the Ni valence is not determined only by z, but is a function of x and y. If z=0 and y=0, the Ni valence remains divalent regardless of the value of x. If z is a negative value, it means that the amount of Li contained in the active material is insufficient compared to the stoichiometric amount, and if the value is too negative, the effect of the present invention may not be obtained. On the other hand, even if the z value is the same, the Ni valence is higher as the composition becomes Ni-rich (large y value) and / or Co-rich (large x value), and when used in a battery, the rate characteristics and output characteristics are improved, but on the other hand, the capacity is likely to decrease. For this reason, it can be said that it is more preferable to define the upper and lower limits of the z value as functions of x and y. Furthermore, when the x value is in the range of 0≦x≦0.1, that is, the amount of Co is small, not only is the cost reduced, but also the charge / discharge capacity, cycle characteristics, and safety are improved when the battery is used as a nonaqueous electrolyte battery designed to be charged at a high charging potential.

[0170] (3) pH The pH of the aqueous solution of the lithium transition metal compound is not particularly limited, but is preferably 11 or more because the gas generation suppression effect by the combination with the monofluorophosphate and / or difluorophosphate contained in the electrolyte is easily manifested. Also, the pH is more preferably 11.2 or more, even more preferably 11.4 μmol / g or more, particularly preferably 11.6 or more, and most preferably 11.8 or more. The limit is preferably 13 or less, more preferably 12.7 or less, particularly preferably 12.4 or less, and most preferably 12 or less, in order to reduce gas generation due to side reactions. The pH of the lithium transition metal compound is measured by weighing 50 g of desalted water into a beaker, adding 5 g of the sample while stirring, and monitoring the liquid temperature and pH value. The pH value and liquid temperature are measured 10 minutes after the addition.

[0171] (4) Carbonates The positive electrode active material may contain a carbonate. The content of the carbonate that can be contained in the positive electrode active material is not particularly limited, but is preferably 10 μmol / g or more because the gas generation suppression effect by the combination with the monofluorophosphate and / or difluorophosphate contained in the electrolyte is easily manifested. In addition, it is more preferably 20 μmol / g or more, even more preferably 40 μmol / g or more, particularly preferably 60 μmol / g or more, and most preferably 80 μmol / g or more. In addition, the upper limit is preferably 100 μmol / g or less, more preferably 98 μmol / g or less, particularly preferably 96 μmol / g or less, and most preferably 94 μmol / g or less, because gas generation due to side reactions is reduced. The carbonate contained in the lithium transition metal compound can be measured, for example, by water extraction ion chromatography.

[0172] (5) Tap density The lithium transition metal compound constituting the positive electrode active material is usually a powder, and the tap density thereof is, but is not limited to, 1.8 g / cm 3 A density of 2 g / cm or more is preferable because the charge / discharge capacity of the battery is large. 3 More preferably, it is 2.1 g / cm or more. 3 More preferably, it is 2.2 g / cm or more. 3 It is particularly preferable that the content is 2.3 g / cm or more. 3 The most preferable value is 4.0 g / cm3 or more because the output characteristics are sufficient. 3 It is preferable that the density is 3.8 g / cm or less. 3 More preferably, it is 3.6 g / cm or less. 3 It is particularly preferable that the content is 3.4 g / cm or less. 3 Most preferably, it is:

[0173] By using a lithium transition metal compound having a high tap density, a high-density positive electrode can be formed. When the tap density of the lithium transition metal compound is within the above range, the amount of the dispersion medium required for forming the positive electrode is appropriate, and the amounts of the conductive material and binder are also appropriate, so that the filling rate of the lithium transition metal compound in the positive electrode is not restricted, and the effect on the battery capacity is also reduced.

[0174] The sample was dropped into a 10 mL graduated cylinder to fill the volume, and then tapped 200 times to calculate the density from the volume and mass of the sample. The tap density calculated by this measurement is defined as the tap density of the lithium transition metal compound in the present invention. The tap density of lithium transition metal compounds was measured by passing them through a sieve with a mesh size of 300 μm at 20 cm 3 After dropping a sample into the tapping cell to fill the cell volume, a powder density measuring device (e.g., Tap Denser manufactured by Seishin Enterprise Co., Ltd.) may be used to perform tapping 200 times with a stroke length of 10 mm, and the density may be calculated from the volume and mass of the sample at that time. Alternatively, the density can be calculated simply by dropping a sample into a 10 mL measuring cylinder to fill it to its volume, then tapping it 200 times, and calculating the density from the volume and mass of the sample at that time.

[0175] (6) Surface coating The lithium transition metal compound has a substance (hereinafter referred to as "surface-attached substance") attached to its surface that has a different composition from the substance that constitutes the main lithium transition metal compound. Examples of the surface-attaching substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate, and carbon.

[0176] These surface attachment substances can be attached to the surface of the lithium transition metal compound by, for example, a method of dissolving or suspending the substance in a solvent, impregnating the lithium transition metal compound, and then drying the resulting solution, a method of dissolving or suspending a surface attachment substance precursor in a solvent, impregnating the lithium transition metal compound, and then reacting the surface attachment substance by heating or the like, a method of adding the surface attachment substance precursor to a lithium transition metal compound precursor, and simultaneously baking the surface attachment substance, etc. When carbon is attached, a method of mechanically attaching the carbonaceous material, for example, in the form of activated carbon, etc., after the surface attachment is completed can also be used.

[0177] The mass of the surface-attached substance attached to the surface of the lithium transition metal compound is preferably 0.1 ppm or more, more preferably 1 ppm or more, and even more preferably 10 ppm or more, relative to the mass of the lithium transition metal compound, and is preferably 20% or less, more preferably 10% or less, and even more preferably 5% or less. The surface-attached substance can suppress the oxidation reaction of the non-aqueous electrolyte on the surface of the lithium transition metal compound, thereby improving the battery life. In addition, when the amount of the attached substance is within the above range, the effect can be fully exerted, and the inflow and outflow of lithium ions is not hindered, and the resistance is not likely to increase.

[0178] (7) Shape The shape of the lithium transition metal compound may be any of the conventional shapes such as block, polyhedron, sphere, oval sphere, plate, needle, column, etc. Primary particles may be aggregated to form secondary particles, and the secondary particles may have a spherical or oval sphere shape.

[0179] (8) Median diameter d50 The median diameter d50 of the lithium transition metal compound (the secondary particle diameter when primary particles are aggregated to form secondary particles) can be measured using a laser diffraction / scattering type particle size distribution measuring device. The median diameter d50 is preferably 0.1 μm or more, more preferably 0.5 μm or more, even more preferably 1 μm or more, particularly preferably 3 μm or more, and also preferably 30 μm or less, more preferably 20 μm or less, even more preferably 16 μm or less, and particularly preferably 15 μm or less. When the median diameter d50 is within the above range, it becomes easy to obtain a high bulk density product, and furthermore, since it does not take time for lithium to diffuse within the particles, the battery characteristics are less likely to deteriorate. In addition, when preparing the positive electrode of a battery, that is, when the active material, conductive material, binder, etc. are slurried with a solvent and applied in a thin film, streaking is also less likely to occur.

[0180] In addition, by mixing two or more kinds of lithium transition metal compounds having different median diameters d50 in any ratio, the filling property during the preparation of the positive electrode can be further improved. The median diameter d50 of the lithium transition metal compound is measured by using a 0.1 mass% sodium hexametaphosphate aqueous solution as a dispersion medium and a particle size distribution meter (e.g., LA-920 manufactured by Horiba, Ltd.) to measure the lithium transition metal compound dispersion liquid after ultrasonic dispersion for 5 minutes, setting the measurement refractive index to 1.24.

[0181] (9) Average primary particle diameter When the primary particles are aggregated to form secondary particles, the average primary particle size of the lithium transition metal compound is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.08 μm or more, particularly preferably 0.1 μm or more, and preferably 3 μm or more. Within the above range, spherical secondary particles are easily formed, powder packing is appropriate, and a sufficient specific surface area can be secured, thereby suppressing a decrease in battery performance such as output characteristics. The average primary particle size of the lithium transition metal compound is measured by observation using a scanning electron microscope (SEM). Specifically, in a photograph at a magnification of 10,000 times, the longest intercept value of the horizontal line at the left and right boundaries of the primary particle is calculated for any 50 primary particles, and the average value is calculated.

[0182] (10)BET specific surface area The BET specific surface area of ​​the lithium transition metal compound is preferably 0.2 m or less, as measured by the BET method. 2 ·g -1 Above 0.3m 2 ·g -1 More preferably, 0.4m or more 2 ·g -1 More preferably, the length is 4.0 m or more. 2 ·g -1 Less than 2.5m 2 ·g -1 Less than 1.5m is preferable. 2 ·g -1 The following is more preferable. When the BET specific surface area is within the above range, it is easy to prevent the deterioration of battery performance. Furthermore, a sufficient tap density can be secured, and the coating property during the formation of the positive electrode is good.

[0183] The BET specific surface area of ​​the lithium transition metal compound is measured using a surface area meter (e.g., a fully automatic surface area measuring device manufactured by Ohkura Riken Co., Ltd.). Specifically, the sample is pre-dried for 30 minutes at 150°C under nitrogen flow, and then measured by a nitrogen adsorption BET one-point method using a gas flow method, using a nitrogen-helium mixed gas accurately adjusted so that the relative pressure of nitrogen to atmospheric pressure is 0.3. The specific surface area determined by this measurement is defined as the BET specific surface area of ​​the lithium transition metal compound in the present invention.

[0184] (Method for producing positive electrode active material containing lithium transition metal compound) The method for producing the positive electrode active material containing a lithium transition metal compound is not particularly limited as long as it does not deviate from the gist of the present invention, but several methods can be mentioned, and a method generally used for producing inorganic compounds can be used. In particular, various methods can be considered for producing spherical or oval-spherical positive electrode active materials. One example is a method in which transition metal raw materials such as transition metal nitrates or sulfates, and raw materials of other elements as necessary, are dissolved or pulverized and dispersed in a solvent such as water, and the pH is adjusted while stirring to produce and recover a spherical precursor, which is dried as necessary, and then a Li source such as LiOH, Li2CO3, or LiNO3 is added and the mixture is fired at high temperature to obtain the positive electrode active material.

[0185] Another example of the method is to dissolve or pulverize and disperse a transition metal raw material such as a transition metal nitrate, sulfate, hydroxide, or oxide, and, if necessary, raw materials of other elements, in a solvent such as water, and then dry and mold the resulting material using a spray dryer or the like to form a spherical or ellipsoidal precursor. To this, a Li source such as LiOH, Li2CO3, or LiNO3 is added, and the mixture is baked at high temperature to obtain a positive electrode active material.

[0186] As yet another example of the method, a transition metal raw material such as a transition metal nitrate, sulfate, hydroxide or oxide, a Li source such as LiOH, Li2CO3 or LiNO3, and, as necessary, raw materials of other elements are dissolved or pulverized and dispersed in a solvent such as water, and then dried and molded using a spray dryer or the like to form a spherical or ellipsoidal precursor, which is then calcined at a high temperature to obtain a positive electrode active material.

[0187] In addition, in selecting a transition metal raw material, the sulfate content and carbonate content of the positive electrode active material described above can be set to desired values ​​by adjusting the amounts of sulfate and carbonate used, adjusting the firing temperature, and / or performing washing, etc. The lithium transition metal compound used for the positive electrode active material may be one of the above. It is also possible to use a blend of two or more of these. It is also possible to use a blend of these with sulfides, phosphate compounds, other lithium transition metal composite oxides, etc. As the sulfides, compounds having a two-dimensional layer structure such as TiS2 and MoS2, and compounds having the general formula Me xExamples of the lithium transition metal complex oxide include those having a spinel structure that allows three-dimensional diffusion, and those having a layered structure that allows two-dimensional diffusion of lithium ions. Those having a spinel structure are generally represented as LiMe2O4 (Me is at least one or more transition metals), and specifically include LiFePO4, LiCoPO4, LiNiPO4, LiMnPO4, and the like. Those having a spinel structure are generally represented as LiMe2O4 (Me is at least one or more transition metals), and specifically include LiMn2O4, LiCoMnO4, LiNi 0.5 Mn 1.5 O4, LiCoVO4, etc. Those with layered structures are specifically LiCoO2, LiNiO2, LiNi 1-x Co x O2, LiNi 1-x-y Co x Mn y O2, LiNi 0.5 Mn 0.5 O2, Li 1.2 Cr 0.4 Mn 0.4 O2, Li 1.2 Cr 0.4 Ti 0.4 O2, LiMnO2, etc.

[0188] <Construction and preparation method of positive electrodes for non-aqueous electrolyte batteries> The positive electrode for a non-aqueous electrolyte battery is formed by forming a layer of a positive electrode active material containing the above-mentioned lithium transition metal compound and a binder on a current collector. The layer of the positive electrode active material is usually produced by dry-mixing a positive electrode active material containing a lithium transition metal compound, a binder, and optionally a conductive material, a thickener, and the like, into a sheet, which is then pressed onto the positive electrode current collector; alternatively, these materials are dissolved or dispersed in a liquid medium to form a slurry, which is then applied to the positive electrode current collector and dried.

[0189] The material of the positive electrode current collector is usually a metal material such as aluminum, stainless steel, nickel plating, titanium, tantalum, etc., or a carbon material such as carbon cloth, carbon paper, etc. In addition, the shape of the positive electrode current collector may be, for example, a metal foil, a metal cylinder, a metal coil, a metal plate, a metal thin film, an expanded metal, a punched metal, a foamed metal, etc. in the case of a metal material, or a carbon plate, a carbon thin film, a carbon cylinder, etc. in the case of a carbon material.

[0190] The thin film may be formed in a mesh shape as appropriate. The binder used in producing the layer of the positive electrode active material is not particularly limited. In the case of a coating method, any material may be used as long as it is stable in the liquid medium used in producing the electrode. Specific examples include resin-based polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, aromatic polyamide, cellulose, and nitrocellulose; rubber-like polymers such as SBR (styrene-butadiene rubber), NBR (acrylonitrile-butadiene rubber), fluororubber, isoprene rubber, butadiene rubber, and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers and hydrogenated products thereof; and EPDM (ethylene-propylene copolymer). Examples of suitable materials include thermoplastic elastomeric polymers such as styrene-ethylene-butadiene-ethylene copolymers, styrene-isoprene-styrene block copolymers, and their hydrogenated products; soft resinous polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, and propylene-α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymers; and polymer compositions having ionic conductivity for alkali metal ions (especially lithium ions).

[0191] These substances may be used alone or in any combination of two or more in any ratio. The proportion of the binder in the positive electrode active material layer is usually 0.1 mass % or more and 80 mass % or less. If the proportion of the binder is too low, the lithium transition metal compound cannot be sufficiently held, and the mechanical strength of the positive electrode is reduced. If the concentration is insufficient, the battery performance such as cycle characteristics may deteriorate, whereas if the concentration is too high, the battery capacity and conductivity may decrease.

[0192] The positive electrode active material layer usually contains a conductive material to increase the electrical conductivity. There are no particular limitations on the type, but specific examples include metal materials such as copper, nickel, etc., graphite such as natural graphite, artificial graphite, etc., carbon black such as acetylene black, and amorphous carbon such as needle coke, etc. These substances may be used alone or in any combination of two or more in any ratio.

[0193] The proportion of the conductive material in the positive electrode active material layer is usually 0.01% by mass or more and 50% by mass or less. If the proportion of the conductive material is too low, the conductivity may be insufficient, and conversely, if it is too high, the battery capacity may decrease. The liquid medium for forming the slurry is not particularly limited in type, and may be either an aqueous solvent or an organic solvent, as long as it is capable of dissolving or dispersing the positive electrode active material containing a lithium transition metal compound as the positive electrode material, the binder, and the conductive material and thickener used as necessary. Examples of aqueous solvents include water and alcohol, and examples of organic solvents include N-methylpyrrolidone (NMP), dimethylformamide, dimethylacetamide, methyl ethyl ketone, cyclohexanone, methyl acetate, methyl acrylate, diethyltriamine, N,N-dimethylaminopropylamine, ethylene oxide, tetrahydrofuran (THF), toluene, acetone, dimethyl ether, dimethylacetamide, hexamethylphosphatamide, dimethylsulfoxide, benzene, xylene, quinoline, pyridine, methylnaphthalene, hexane, etc. In particular, when an aqueous solvent is used, a dispersant is added together with the thickener, and a slurry is formed using latex such as SBR.

[0194] These solvents may be used alone or in any combination of two or more in any ratio. The content of the lithium transition metal compound as the positive electrode material in the positive electrode active material layer is usually 10 mass % or more and 99.9 mass % or less. If the content of the lithium transition metal compound in the positive electrode active material layer is too high, the strength of the positive electrode tends to be insufficient, and if it is too low, the capacity may be insufficient.

[0195] The thickness of the positive electrode active material layer is usually about 10 to 200 μm. The density of the positive electrode after pressing is not particularly limited, but is preferably 3.0 g / cm 3 It is preferable that the density is 3.2 g / cm or more because it is possible to obtain a high capacity battery. 3 More preferably, it is 3.4 g / cm or more. 3 It is particularly preferable that the content is 3.6 g / cm or more. 3 The most preferable upper limit is 4.2 g / cm because it is difficult for the input / output characteristics to deteriorate. 3 It is preferable that the density is 4.1 g / cm or less. 3 More preferably, it is 4.0 g / cm or less. 3 It is particularly preferable that the content is 3.9 g / cm or less. 3 Most preferably, it is: The positive electrode active material layer obtained by coating and drying is preferably compressed by a roller press or the like in order to increase the packing density of the positive electrode active material.

[0196] [2-4. Separator] A separator is usually interposed between the positive electrode and the negative electrode to prevent short circuiting. In this case, the non-aqueous electrolyte is usually impregnated into the separator before use. The material and shape of the separator are not particularly limited, and any known material can be used as long as it does not significantly impair the effects of the present invention. Among them, a porous sheet made of a material stable against a non-aqueous electrolyte, such as a resin, glass fiber, or inorganic material, and having excellent liquid retention properties is used. Alternatively, it is preferable to use a material in the form of a nonwoven fabric. Examples of materials that can be used for the resin or glass fiber separator include polyolefins such as polyethylene and polypropylene, aromatic polyamides, polytetrafluoroethylene, polyethersulfone, and glass filters. Among these, glass filters and polyolefins are preferred, and polyolefins are more preferred. These materials may be used alone or in any combination and ratio of two or more.

[0197] The thickness of the separator is not limited, but is usually 1 μm or more, preferably 5 μm or more, and more preferably 10 μm or more, and is usually 50 μm or less, preferably 40 μm or less, and more preferably 30 μm or less. If the separator is thinner than the above range, the insulating properties and mechanical strength may decrease, whereas if the separator is thicker than the above range, not only may the battery performance such as rate characteristics decrease, but also the energy density of the nonaqueous electrolyte battery as a whole may decrease.

[0198] Furthermore, when a porous material such as a porous sheet or nonwoven fabric is used as the separator, the porosity of the separator is optional, but is usually 20% or more, preferably 35% or more, and more preferably 45% or more, and is usually 90% or less, preferably 85% or less, and more preferably 75% or less. If the porosity is too low, the membrane resistance increases and the rate characteristics tend to deteriorate, whereas if the porosity is too high, the mechanical strength of the separator tends to decrease and the insulating properties tend to deteriorate.

[0199] The average pore size of the separator is also optional, but is usually 0.5 μm or less, preferably 0.2 μm or less. Also, it is usually 0.05 μm or more. If the average pore size exceeds the above range, short circuits are likely to occur. If it is below the above range, the membrane resistance increases and the rate characteristics may deteriorate. On the other hand, examples of inorganic materials that can be used include oxides such as alumina and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates such as barium sulfate and calcium sulfate, and these are in particulate or fibrous form.

[0200] The separator may be in the form of a thin film such as a nonwoven fabric, a woven fabric, or a microporous film. In the thin film form, a film with a pore size of 0.01 to 1 μm and a thickness of 5 to 50 μm is preferably used. In addition to the above independent thin film form, a separator may be used in which a composite porous layer containing the above inorganic particles is formed on the surface layer of the positive electrode and / or negative electrode using a resin binder. For example, a porous layer may be formed on both sides of the positive electrode using alumina particles with a 90% particle size of less than 1 μm and a fluororesin as a binder.

[0201] The characteristics of the separator in a non-electrolyte secondary battery can be understood by the Gurley value. The Gurley value indicates the difficulty of air passing through in the film thickness direction, and is expressed as the number of seconds required for 100 ml of air to pass through the film, so that a smaller value means that air passes through easily, and a larger value means that air passes through less easily. In other words, a smaller value means that the film has better interconnectivity in the thickness direction, and a larger value means that the film has worse interconnectivity in the thickness direction. Interconnectivity is the degree of connection of holes in the film thickness direction. If the separator of the present invention has a low Gurley value, it can be used for various purposes. For example, when used as a separator for a non-aqueous electrolyte battery, a low Gurley value means that lithium ions are easily transferred, and is preferable because it has excellent battery performance. The Gurley value of the separator is arbitrary, but is preferably 10 to 1000 seconds / 100 ml, more preferably 15 to 800 seconds / 100 ml, and even more preferably 20 to 500 seconds / 100 ml. If the Gurley value is 1000 seconds / 100 ml or less, the electrical resistance is substantially low, which is preferable for the separator.

[0202] [2-5.Battery design] <Electrode group> The electrode group may have either a laminated structure in which the positive electrode plate and the negative electrode plate are sandwiched between the separator, or a structure in which the positive electrode plate and the negative electrode plate are spirally wound with the separator between them.

[0203] The ratio of the volume of the electrode group to the internal volume of the battery (hereinafter referred to as the electrode group occupancy rate) is usually 40% or more, preferably 50% or more, and usually 90% or less, preferably 80% or less. If the electrode group occupancy rate is below the above range, the battery capacity will be small, while if it exceeds the above range, the void space will be small, and the battery will become hot, causing the members to expand and the vapor pressure of the electrolyte liquid component to increase, resulting in an increase in internal pressure, which will degrade various characteristics of the battery, such as repeated charge / discharge performance and high-temperature storage, and may even cause the gas release valve that releases the internal pressure to operate.

[0204] <Outer case> The material of the exterior case is not particularly limited as long as it is a material that is stable against the non-aqueous electrolyte used. Specifically, metals such as nickel-plated steel sheet, stainless steel, aluminum or aluminum alloy, magnesium alloy, etc., and laminated films of resin and aluminum foil are used. From the viewpoint of weight reduction, metals such as aluminum or aluminum alloy, and laminated films are preferably used.

[0205] Examples of exterior cases using metals include those in which metals are welded to each other by laser welding, resistance welding, or ultrasonic welding to form a sealed, airtight structure, and those in which the above-mentioned metals are used with a resin gasket interposed between them to form a crimped structure. In the case of the exterior case using the laminate film, a sealed and sealed structure is formed by heat-sealing resin layers, etc. In order to improve the sealing property, a resin different from the resin used in the laminate film may be interposed between the resin layers. In particular, when the resin layer is heat-sealed via the current collecting terminal to form a sealed structure, a bond is formed between metal and resin, so a resin having a polar group or a modified resin into which a polar group has been introduced is preferably used as the intervening resin.

[0206] <Protection element> The protective element may be a PTC (Positive Temperature Coefficient) whose resistance increases when abnormal heat is generated or an excessive current flows, a thermal fuse, a thermistor, a valve (current cutoff valve) that cuts off the current flowing in the circuit due to a sudden increase in the battery's internal pressure or temperature when abnormal heat is generated, etc. It is preferable to select the above protective element so that it will not operate under normal use at high current, and it is even more preferable to design it so that abnormal heat generation or thermal runaway does not occur even without the protective element.

[0207] <Exterior body> The non-aqueous electrolyte battery of the present invention is usually constructed by housing the above-mentioned non-aqueous electrolyte, negative electrode, positive electrode, separator, etc. in an exterior body. This exterior body is not particularly limited, and any known exterior body can be used as long as it does not significantly impair the effects of the present invention. Specifically, the material of the exterior body is arbitrary, but usually, for example, nickel-plated iron, stainless steel, aluminum or its alloy, nickel, titanium, etc. are used. The shape of the exterior body is also arbitrary, and may be, for example, cylindrical, rectangular, laminated, coin-shaped, large, or the like.

[0208] <Battery voltage> The nonaqueous electrolyte battery of the present invention is usually used at a battery voltage of 4.0 V or more. The battery voltage is preferably 4.1 V or more, more preferably 4.15 V or more, and most preferably 4.2 V or more. This is because increasing the battery voltage can increase the energy density of the battery.

[0209] On the other hand, when the battery voltage is increased, the potential of the positive electrode increases, and the problem of side reactions on the positive electrode surface increases. By using the electrolyte and battery of the present invention, the above problem can be solved, but if the voltage is too high, the amount of side reactions on the positive electrode surface becomes too large, which deteriorates the battery characteristics. Therefore, the upper limit of the battery voltage is preferably 5V or less, more preferably 4.8V or less, and most preferably 4.6V or less.

[0210] <Reasons why the present invention is effective> The reason why the present invention is effective is not yet clear, but is presumed to be as follows. First, attempts have been made to use high-capacity lithium transition metal compounds as positive electrode active materials in automotive batteries, which can be achieved, for example, by increasing the amount of Ni.

[0211] However, problems have been found with such lithium transition metal compounds, in that when used in a non-aqueous electrolyte battery, there is a large capacity loss, a large amount of gas generation, and a large increase in resistance after storage at high temperatures. As a result of the inventors' investigation, the following mechanism was inferred. In other words, when a high-capacity lithium transition metal compound is used, the oxygen atoms in the crystals of the lithium transition metal compound become unstable and activated during charging. This is thought to increase the oxidizing power of the positive electrode. In addition, it is presumed that the lithium transition metal compound in this state reacts with the electrolyte in the battery to generate gas, which deteriorates the surface of the lithium transition metal compound, reducing the capacity and increasing the resistance.

[0212] In response to this, the inventors discovered that by incorporating both a specific cyclic acid anhydride and a specific sulfonic acid compound in the electrolyte, the oxidizing power on the surface of the positive electrode can be reduced, and capacity loss and resistance increase after high-temperature storage, as well as gas generation due to decomposition of the electrolyte solvent, can be suppressed. The reason for this is not yet clear, but it is speculated that the specific cyclic acid anhydride reacts with the surface of the lithium transition metal compound with increased oxidizing power to form a coating, which reduces the oxidizing power of the surface of the specific cyclic acid positive electrode and suppresses the decomposition of the electrolyte solvent. At this time, a coating derived from the specific cyclic acid anhydride grows due to high-temperature storage, causing capacity loss and resistance increase, but by further adding a specific sulfonic acid compound, it is speculated that the oxidizing power of the lithium transition metal compound can be reduced while suppressing the growth of the coating, and the capacity loss and increase in resistance after high-temperature storage, as well as gas generation due to decomposition of the electrolyte, can be suppressed. EXAMPLES

[0213] Next, specific embodiments of the present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples. The abbreviations for the compounds used in the examples are shown below. Compound 1: Allylsuccinic anhydride Compound 2: Lithium fluorosulfonate Compound 3: Lithium difluorophosphate Compound 4: Succinic anhydride

[0214] [Examples 1-2, Comparative Examples 1-4] [Preparation of non-aqueous electrolyte battery] <Preparation of non-aqueous electrolyte> In a dry argon atmosphere, 1 mol / L (as the content in the non-aqueous electrolyte) of LiPF6 that had been thoroughly dried was dissolved in a mixture of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate (volume ratio 3:4:3), and further, 2 mass% of vinylene carbonate (as the content in the non-aqueous electrolyte) and 5 mass% of fluoroethylene carbonate (as the content in the non-aqueous electrolyte) were dissolved to prepare a non-aqueous electrolyte solution as a reference electrolyte solution 1. The compounds 1 to 3 were dissolved as additives in the combinations and contents shown in Table 1 below in this reference electrolyte solution 1 to prepare the non-aqueous electrolyte solutions of each Example and Comparative Example. In addition, the "content (mass%)" in the table is the content when the reference electrolyte solution 1 is taken as 100 mass%.

[0215] [Table 1]

[0216] Using this nonaqueous electrolyte, a nonaqueous electrolyte battery was produced by the following method, and the evaluations described below were carried out. <Preparation of positive electrode> The lithium nickel manganese cobalt composite oxide used as the positive electrode active material is NMC622(Li 1.00 Ni 0.61 Mn 0.19 Co 0.20 The positive electrode active material (94 parts by mass), acetylene black (3 parts by mass) as a conductive material, polyvinylidene fluoride (PVdF) (3 parts by mass) as a binder, and polyvinylpyrrolidone (0.07 parts by mass) as a dispersant were mixed and slurried in N-methyl-2-pyrrolidone, and the mixture was uniformly applied to an aluminum foil having a thickness of 15 μm and dried. The positive electrode was then roll pressed to obtain a positive electrode. The plate density of the positive electrode was 3.3 g / cm. 3 It was.

[0217] <Preparation of negative electrode> 49 parts by mass of graphite powder was mixed with 50 parts by mass of an aqueous dispersion of sodium carboxymethylcellulose (concentration of sodium carboxymethylcellulose: 1% by mass) as a thickener and 1 part by mass of an aqueous dispersion of styrene-butadiene rubber (concentration of styrene-butadiene rubber: 49% by mass) as a binder, and mixed in a disperser to form a slurry. The obtained slurry was uniformly applied to a copper foil with a thickness of 10 μm, dried, and roll-pressed to form a negative electrode.

[0218] <Manufacture of non-aqueous electrolyte batteries> The positive electrode, the negative electrode, and the polyolefin separator were laminated in this order, and the battery element thus obtained was wrapped in an aluminum laminate film, and the nonaqueous electrolyte was injected and then vacuum sealed to prepare a sheet-shaped nonaqueous electrolyte battery.

[0219] [Evaluation of non-aqueous electrolyte batteries] ·Initial charge / discharge In a thermostatic bath at 25°C, a sheet-shaped non-aqueous electrolyte battery was charged at a constant current of 0.05C (the current value at which the rated capacity based on the discharge capacity at a 1-hour rate is discharged in 1 hour is defined as 1C; the same applies below) to 3.7V, then charged at a constant current / constant voltage of 0.2C to a voltage of 4.3V, and then discharged at a constant current of 0.2C to 2.5V.

[0220] Furthermore, the nonaqueous electrolyte battery was stabilized by charging at a constant current and constant voltage at 0.2C to 4.1V and then storing the battery at 60°C for 12 hours. The battery was then discharged at a constant current to 2.5V at 25°C, and the ratio (%) of the discharge capacity at this time to the charge capacity before storage at 60°C was taken as the capacity retention rate. The battery was then charged at a constant current and constant voltage at 0.2C to a voltage of 4.3V, and then discharged at a constant current of 0.2C to 2.5V to complete the initial charge and discharge.

[0221] Next, constant current-constant voltage charging was performed at 0.2C up to a voltage of 3.7V, and then the cells were discharged at 0.05C, 0.1C, 0.25C, and 0.5C for 10 seconds at -10°C, and the voltage at the 10th second was measured. The initial discharge resistance (Ω) was calculated from the gradient of the current-voltage line. The cells were also charged at 0.05C, 0.1C, 0.15C, and 0.25C for 10 seconds at -10°C, and the voltage at the 10th second was measured. The initial charge resistance (Ω) was calculated from the gradient of the current-voltage line. Thereafter, constant current-constant voltage charging was carried out at 0.2 C up to a voltage of 4.3 V.

[0222] High temperature storage test The nonaqueous electrolyte battery after the above initial charge and discharge was immersed in an ethanol bath and the volume was measured, which was the volume before high-temperature storage. Next, the nonaqueous electrolyte battery after the initial charge and discharge was stored at high temperature at 60°C for 2 weeks. After that, the nonaqueous electrolyte battery was sufficiently cooled, and then immersed in an ethanol bath and the volume was measured. The amount of gas generated was calculated from the change in volume before and after the high-temperature storage test, which was the amount of gas generated.

[0223] This non-aqueous electrolyte battery was placed in a thermostatic chamber at 25°C and discharged at a constant current of 0.2C to 2.5V, then charged at a constant current and constant voltage of 0.2C to a voltage of 3.7V. It was then discharged at 0.05C, 0.1C, 0.25C, and 0.5C for 10 seconds at -10°C, and the voltage at the 10th second was measured. The discharge resistance after storage (Ω) was calculated from the slope of the current-voltage line. It was also discharged at 0.05C, 0.1C, 0.15C, and 0.25C for 10 seconds at -10°C. The battery was charged for 10 seconds, and the voltage was measured at 10 seconds. The post-storage charge resistance (Ω) was calculated from the slope of the current-voltage curve.

[0224] The discharge resistance increase rate (%) was calculated as "discharge resistance increase rate = (discharge resistance after storage - initial discharge resistance) / initial discharge resistance × 100", and the charge resistance increase rate (%) was calculated as "charge resistance increase rate = (charge resistance after storage - initial charge resistance) / initial discharge resistance × 100". It is preferable that the capacity retention rate is higher since the capacity becomes higher, and it is preferable that the discharge resistance increase rate, charge resistance increase rate and gas generation amount are smaller since the deterioration and swelling of the nonaqueous electrolyte battery becomes smaller.

[0225] Table 1 shows the results of evaluating the capacity retention rate, discharge resistance increase rate, charge resistance increase rate, and gas generation amount of the nonaqueous electrolyte batteries of each Example and Comparative Example. As is clear from Table 1, when compounds 1 and 2 or compounds 1 to 3 are added to the nonaqueous electrolyte, the capacity retention rate, discharge resistance increase rate, charge resistance increase rate, and gas generation amount are improved compared to the case where only one of compounds 1 to 3 is contained. In other words, a nonaqueous electrolyte battery with high capacity, little deterioration after high-temperature storage, and little swelling is obtained.

[0226] [Examples 3 to 4, Comparative Examples 5 to 9] [Preparation of non-aqueous electrolyte battery] <Preparation of non-aqueous electrolyte> The nonaqueous electrolyte solutions of the Examples and Comparative Examples were prepared by dissolving the compounds 2 to 4 as additives in the reference electrolyte solution 1 in the combinations and contents shown in Table 2 below. Note that the "content (mass%)" in the table is the content when the reference electrolyte solution 1 is taken as 100 mass%.

[0227] [Table 2]

[0228] [Evaluation of non-aqueous electrolyte batteries] ·Initial charge / discharge In a thermostatic bath at 25°C, a sheet-shaped non-aqueous electrolyte battery was charged at a constant current of 0.05C (the current value at which the rated capacity based on the discharge capacity at a 1-hour rate is discharged in 1 hour is defined as 1C; the same applies below) to 3.7V, then charged at a constant current / constant voltage of 0.2C to a voltage of 4.2V, and then discharged at a constant current of 0.2C to 2.5V.

[0229] Furthermore, the nonaqueous electrolyte battery was charged at a constant current and constant voltage of 0.2 C up to 4.1 V, and then stored at 45°C for 72 hours to stabilize the nonaqueous electrolyte battery. After that, the battery was discharged at a constant current up to 2.5 V at 25°C, and the ratio (% Further, constant current / constant voltage charging was performed at 0.2 C up to a voltage of 4.2 V, and then constant current discharging was performed at 0.2 C up to 2.5 V to complete the initial charge / discharge.

[0230] Next, constant current-constant voltage charging was performed at 0.2C up to a voltage of 3.7V, and then the cells were discharged at 0.05C, 0.1C, 0.25C, and 0.5C for 10 seconds at -10°C, and the voltage at the 10th second was measured. The initial discharge resistance (Ω) was calculated from the gradient of the current-voltage line. The cells were also charged at 0.05C, 0.1C, 0.15C, and 0.25C for 10 seconds at -10°C, and the voltage at the 10th second was measured. The initial charge resistance (Ω) was calculated from the gradient of the current-voltage line. Thereafter, constant current-constant voltage charging was carried out at 0.2 C up to a voltage of 4.2 V.

[0231] High temperature storage test The nonaqueous electrolyte battery after the above initial charge and discharge was immersed in an ethanol bath and the volume was measured, which was the volume before high-temperature storage. Next, the nonaqueous electrolyte battery after the initial charge and discharge was stored at high temperature at 85°C for 24 hours. After that, the nonaqueous electrolyte battery was sufficiently cooled, and then immersed in an ethanol bath and the volume was measured. The amount of gas generated was calculated from the change in volume before and after the high-temperature storage test, which was the amount of gas generated.

[0232] The non-aqueous electrolyte battery was placed in a thermostatic chamber at 25°C, discharged at a constant current of 0.2C to 2.5V, then charged at a constant current and constant voltage of 0.2C to a voltage of 3.7V, and then discharged at 0.05C, 0.1C, 0.25C, and 0.5C for 10 seconds at -10°C, and the voltage at the 10th second was measured. The discharge resistance after storage (Ω) was calculated from the gradient of the current-voltage line. The battery was also charged at 0.05C, 0.1C, 0.15C, and 0.25C for 10 seconds at -10°C, and the voltage at the 10th second was measured. The charge resistance after storage (Ω) was calculated from the gradient of the current-voltage line.

[0233] The discharge resistance increase rate (%) was calculated as "discharge resistance increase rate = (discharge resistance after storage - initial discharge resistance) / initial discharge resistance × 100", and the charge resistance increase rate (%) was calculated as "charge resistance increase rate = (charge resistance after storage - initial charge resistance) / initial discharge resistance × 100". It is preferable that the capacity retention rate is higher since the capacity becomes higher, and it is preferable that the discharge resistance increase rate, charge resistance increase rate and gas generation amount are smaller since the deterioration and swelling of the nonaqueous electrolyte battery becomes smaller.

[0234] Table 2 shows the results of evaluating the capacity retention rate, discharge resistance increase rate, charge resistance increase rate, and gas generation rate of the nonaqueous electrolyte batteries of each Example and Comparative Example. As is clear from Table 2, when compounds 2 and 4, or compounds 2 to 4 are added to the nonaqueous electrolyte, the capacity retention rate, discharge resistance increase rate, charge resistance increase rate, and gas generation rate are improved compared to when only one of compounds 2 to 4, or compounds 2 and 3 are contained. In other words, a nonaqueous electrolyte battery with high capacity, little deterioration after high-temperature storage, and little swelling is obtained. [Industrial Applicability]

[0235] According to the non-aqueous electrolyte of the present invention, the initial characteristics and durability of the non-aqueous electrolyte battery can be improved, which is useful. Therefore, the non-aqueous electrolyte of the present invention and the non-aqueous electrolyte battery using the same can be used for various known applications. Specific examples include notebook computers, pen-input personal computers, mobile personal computers, electronic book players, mobile phones, mobile fax machines, mobile copiers, mobile printers, headphone stereos, video movies, liquid crystal televisions, handy cleaners, portable CDs, mini discs, transceivers, electronic organizers, calculators, memory cards, portable tape recorders, radios, backup power sources, motors, automobiles, motorcycles, motorized bicycles, bicycles, lighting equipment, toys, game equipment, watches, power tools, strobes, cameras, home backup power sources, business backup power sources, load leveling, etc. Examples of such power sources include power sources for electrical appliances, natural energy storage power sources, and lithium ion capacitors.

Claims

1. At least one compound (1) selected from the group consisting of succinic anhydride, maleic anhydride, and allyl succinic anhydride, and LiFSO 3 , LiCH 3 SO 3 and LiCF 3 SO 3 and at least one compound (2) selected from the group consisting of: 2 HCOOC 3 (Except those containing.)

2. The nonaqueous electrolyte solution according to claim 1, wherein the content of the compound (1) in the nonaqueous electrolyte solution is 0.001% by mass or more and 10.0% by mass or less.

3. The nonaqueous electrolyte solution according to claim 1 or 2, wherein the content of the compound (1) in the nonaqueous electrolyte solution is 0.01% by mass or more and 3% by mass or less.

4. The nonaqueous electrolyte solution according to any one of claims 1 to 3, wherein the content of the compound (2) in the nonaqueous electrolyte solution is 0.001 mass% or more and 10.0 mass% or less.

5. The nonaqueous electrolyte solution according to any one of claims 1 to 4, wherein the content of the compound (2) in the nonaqueous electrolyte solution is 0.01 mass% or more and 5 mass% or less.

6. The nonaqueous electrolyte solution according to any one of claims 1 to 5, wherein the ratio (α / β) of the mass (α) of the compound (1) to the mass (β) of the compound (2) is 0.10 or more and 5 or less.

7. The non-aqueous electrolyte according to any one of claims 1 to 6, wherein the non-aqueous electrolyte contains at least one selected from the group consisting of monofluorophosphates and difluorophosphates.

8. The non-aqueous electrolyte according to any one of claims 1 to 7, wherein the non-aqueous electrolyte contains a cyclic carbonate having a carbon-carbon unsaturated bond and / or a fluorine-containing cyclic carbonate.

9. The non-aqueous electrolyte according to any one of claims 1 to 8, except for the non-aqueous electrolyte containing 1,3-dioxane.

10. A non-aqueous electrolyte battery comprising: a positive electrode having a positive electrode active material capable of absorbing and releasing metal ions; a negative electrode having a negative electrode active material capable of absorbing and releasing metal ions; and the non-aqueous electrolyte according to any one of claims 1 to 9.

11. 11. The nonaqueous electrolyte battery according to claim 10, wherein the positive electrode active material comprises a lithium transition metal compound represented by the following composition formula (I): Li 1+x M 4 O 2 ・・・(I) (In the above composition formula (I), x is −0.1 or more and 0.5 or less, M 4 is a plurality of elements including at least Ni and Co, and Ni / M 4 The molar ratio is 0.45 or more and 1.0 or less.)

12. The electrode density of the positive electrode is 3.0 g / cm 3 The nonaqueous electrolyte battery according to claim 10 or 11.

Citation Information

Patent Citations

  • Nonaqueous electrolyte solution and nonaqueous electrolyte battery using the same

    JP2020155254A

  • Electrolytic solution, electrochemical device, lithium ion secondary battery, and module

    WO2019031315A1

  • Nonaqueous electrolyte and nonaqueous electrolyte secondary battery

    JP2013152956A

  • Non-aqueous electrolyte solution and electricity-storage device using same

    WO2013058235A1